Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

Nutrient dynamics and buffering capacity of coastal groundwater-dependent microbialite ecosystems - Carla Dodd; Hayley C. Cawthra; Gudrun Massmann; Janine B. Adams; Callum R. Anderson; Lucienne R.D. Human; Daniel A. Lemley; Tristin W. O'Connell; Gavin M. Rishworth (Estuarine, Coastal and Shelf Science, 2026)

Towards a Refined Definition of “tidal Influence” for the Coastal Wetland Sciences - Ken W. Krauss; Laura S. Brophy; Judith Z. Drexler; Jeffrey A. Kelleway; Janine B. Adams; Havalend E. Steinmuller; Gregory B. Noe; Michael J. Osland; Jamie A. Duberstein; Kurt P. Kowalski; Amanda L. McCutcheon; Kaileʻa M. Annandale; et al. (Wetlands, 2026)

North American crayfish: A quest for the biggest catch - Caitlin C. Bloomer; Susan B. Adams; Zanethia C. Barnett; Zackary A. Graham; Emmy M. Delekta; David M. Hayes; Zachary J. Loughman; Hugh MacIntosh; M. Worth Pugh; Karen Reed; Nathaniel F. Shoobs; Christopher A. Taylor; et al. (Ecology, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

A statistical review of virus reduction in coagulation, flocculation, and sedimentation treatment processes - Mira Chaplin; Lars Andersland; Delaney Snead; Brian M. Pecson; Charles N. Haas; Daniel Gerrity; Adam Olivieri; Tim Dinh; Avery Sanchez; James B. Henderson; Krista R. Wigginton (Water Research, 2026)

Testing water banking recovery policies to secure drought water supply in semi-arid areas with a changing climate - Peter Dillon; Bridget R. Scanlon; Rebecca Bernat; Dennis Gonzalez; Constantin Seidl; Declan Page; Rebecca Doble; John Radcliffe; Adam Hutchinson; Sharon B. Megdal (Groundwater for Sustainable Development, 2026)

Leveraging Pharmacy Education through a Train-the-Trainer Model to Enhance Breast Cancer Literacy in Rural Communities - Christopher L. Farrell; Melanie R. Ginzburg; Morgan B. Enlow; Missouri M. Jenkins; Alexus N. Hames; Cayla R. Adams; Marlana A. Roberts; Hillary E. Stamps; Natalie A. Paxton; Courtney N. Addison; Austin Y. Shull (Journal of Cancer Education, 2026)
Rural versus urban communities experience disproportionate challenges in breast cancer outcomes, with higher breast cancer mortality and later stage disease presentation, despite similar diagnosis rates. These disparities are driven by structural barriers, including rural hospital closures, transportation difficulties, and limited access to oncology specialists. This study evaluated a train-the-trainer program designed to equip PharmD students located at a pharmacy school in a rural county in South Carolina with breast cancer education training, leveraging the pharmacists’ position as accessible healthcare professionals in rural communities. Training focused on breast cancer risk factors, prevention, screening, genetics, staging, and treatment options. Effectiveness was measured through pre- and post-workshop confidence surveys and knowledge assessments. Results showed significant improvement in student confidence across educational domains, with average scores increasing from 6.30 to 8.59 ( p < 0.0001). Understanding of screening guidelines (mean difference: 4.30; p -value: < .0001) and target therapy options showed the greatest improvement (mean difference: 3.65; p -value: < .0001), while knowledge of BRCA gene inheritance showed the smallest change (mean difference: 0.369; p -value: ns), suggesting some pre-existing awareness but limited understanding of its clinical applications. Overall, this pilot program demonstrates how pharmacy education can address healthcare disparities in rural communities. By preparing pharmacists to deliver accurate breast cancer education and to increase rural patient agency, this model creates a sustainable approach to improving health literacy in medically underserved areas. Future research could further expand this model to include diverse healthcare professionals and incorporate long-term impact assessments in community settings.

Dietary nitrate supplementation does not improve resistance exercise performance in resistance-trained women - Sydney N. Brennan; Justin M. Foster; Raymond T. Gerardo; Trevor J. Molnar; Ryan Tran; Christopher B. Sottile; Kyle S. Geppert; Michael Egiazarian; Abigail F. Ballhagen; Money Ghimire; John R. M. Renwick; Lewis A. Gough; et al. (European Journal of Applied Physiology, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

Critical habitats for sharks and rays in Asia remain largely unprotected - Adriana Gonzalez-Pestana; Peter M. Kyne; Emiliano García-Rodríguez; Ryan Charles; Vanessa Bettcher Brito; Asia O. Armstrong; Amanda Batlle-Morera; Marta D. Palacios; Christoph A. Rohner; Giuseppe Notarbartolo di Sciara; Jo Marie V. Acebes; Serena Adam; et al. (Biodiversity and Conservation, 2026)
The Asia region harbors exceptional chondrichthyan (shark, ray, and chimaera) diversity but faces intense fishing pressure. The Important Shark and Ray Areas (ISRA) process provides a collaborative, evidence-based framework to identify critical habitats and inform spatial management. We assessed ISRAs across the Bay of Bengal, Southeast Asia, and the Northwest Pacific to characterize their extent, ecological significance, and conservation relevance. We delineated 122 ISRAs spanning ~ 1 million km 2 (~ 3% of the region) across 12 jurisdictions and international waters, encompassing habitats for 121 species (~ 30% of Asia’s chondrichthyans), 76% of which are threatened. Depleted taxa (e.g., giant guitarfishes, Glaucostegidae) were represented, but charismatic megafauna (e.g., Whale Shark Rhincodon typus ) were overrepresented. In contrast, deepwater and freshwater species were underrepresented. Reproductive Areas were the most common ISRA sub-criterion applied (52% of ISRAs), largely in nearshore zones, while areas for range-restricted species were less frequently (18%) identified. Twelve ISRAs overlapped with biodiversity hotspots, including seven in areas of high overall chondrichthyan species richness and five in areas of high range-restricted species richness. Citizen science was the predominant research method used to delineate ISRAs, while fisheries data were underused despite the region’s major fisheries footprint. Geographic coverage was uneven: Indonesia held the most ISRAs (n = 40; 71.7% of ISRA coverage) while eight jurisdictions (e.g., Viet Nam, China, Republic of Korea) lacked ISRAs due to data gaps. Protection shortfalls are stark: MPAs cover

Simulated wildfire smoke particulate matter elicits STING-dependent astrocyte-mediated inflammatory signaling and neurotoxicity - Adam J. Schuller; Abigail M. Bibb; Megan R. Hager; Omar A. Yanouri; Emma J. Smith; Aidan M. Briggs; Luke B. Montrose; Ronald B. Tjalkens (NeuroToxicology, 2026)

Expanding insights into plant rhabdovirus diversity through the discovery of viruses representing 32 putative novel species - Marleen Botermans; P. P. M. de Koning; M. Westenberg; I. P. Adams; K. Ben Mansour; C. Chabi-Jesus; C. de Krom; A. M. Dullemans; R. Festus; A. R. Fowkes; A. Fox; J. Freitas-Astúa; et al. (Archives of Virology, 2026)
Plant-infecting rhabdoviruses (family Rhabdoviridae , subfamily Betarhabdovirinae ) include several viruses that cause important crop diseases and are subject to phytosanitary regulation. Despite their agricultural and ecological importance, the diversity of plant rhabdoviruses and their impact on plant health remain poorly understood. Here, we report 32 tentative novel species of plant-infecting rhabdoviruses, identified via high-throughput sequencing and spanning nine established genera. The virus sequences originated from diverse hosts and geographic regions, revealing extensive diversity within the family Rhabdoviridae . Several viruses were detected independently in the same host species across multiple countries, demonstrating the practical value of data sharing for confirming host associations and gaining insight into the geographic distribution of these viruses. Our study highlights the underexplored diversity of plant rhabdoviruses and demonstrates the value of coordinated, collaborative virus discovery. With HTS now widely accessible, the challenge has shifted from virus discovery to making sequence data and metadata publicly available, and to conducting the time-consuming biological characterization often deprioritized in favour of viruses with immediate phytosanitary relevance. As a result, many findings remain unreported, leaving valuable data dormant on servers. By sharing genomic data prior to publication, we present an efficient approach to accelerate virus reporting, enable comparative analyses and advance understanding of virus diversity. We hope this collaborative effort will encourage further exploration of plant viruses, including those from hosts without discernable symptoms, supporting virus biology, taxonomy, pest risk assessments, and plant health policies.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Estimating mercury exposure in amphibians using non-lethal tissue sampling - Caitlin T. Rumrill; Kelly L. Smalling; Colleen Emery; Blake R. Hossack; Brian J. Halstead; Michael J. Adams; Adam R. Backlin; Adrianne B. Brand; Jon M. Davenport; Robert N. Fisher; Jill Fleming; Brad M. Glorioso; et al. (Ecotoxicology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Local and Landscape‐Level Environmental Conditions Drive Habitat Selection Across Terrestrial Mammal Species - Björn H. Franke; Aafke M. Schipper; Tal Avgar; Luca Börger; Nilanjan Chatterjee; Thomas Müller; Brian J. Smith; Briana Abrahms; Abdullahi H. Ali; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; et al. (Global Ecology and Biogeography, 2026)
Aim Animal movements are a fundamental process affecting communities and ecosystems. Quantifying habitat selection across species and habitats is key for understanding how animals respond to environmental change. Currently, we lack comparative studies that examine how habitat selection varies across species traits and landscapes. We aim to quantify global patterns of habitat selection to help understand the fundamental drivers of movement behaviour. Location Global. Time Period Contemporary. Major Taxa Studied Terrestrial mammals. Methods We estimated selection coefficients for terrain ruggedness, vegetation productivity, human population density and distance to roads of individual terrestrial mammals through step‐selection analysis of 1344 GPS tracks across 48 species. We quantified intra‐ and interspecific variation and tested whether selection coefficients were associated with species traits and habitat availability. Results We observe an overall avoidance of roads and areas of high human population density as well as rugged terrain, with a large proportion of individuals selecting for areas of intermediate NDVI. However, we also found large intraspecific variation in habitat selection and show that this variation is predicted by local and landscape‐level environmental conditions rather than species traits. Individuals in more remote areas exhibited weaker functional responses to human presence than those in more disturbed areas. Avoidance of rugged terrain is also context‐dependent, with stronger avoidance when local ruggedness is high. The only exception to the observed intraspecific variability is consistent species‐level responses to road proximity. Main Conclusions Our findings contribute to the understanding of habitat selection by terrestrial mammals, showing that selection is largely shaped by environmental conditions and that animals exhibit high plasticity in their responses. Our results also provide further evidence for the significant impact of roads on animal movement. These insights can help us to understand the potential effects of environmental change on the behaviour of mammal species around the world.

Clarifying space use concepts in ecology: Range vs. occurrence distributions - Jesse M. Alston; Christen H. Fleming; Michael J. Noonan; Marlee A. Tucker; Inês Silva; Cody Folta; Thomas S. B. Akre; Abdullahi H. Ali; Jerrold L. Belant; Dean Beyer; Niels Blaum; Katrin Böhning‐Gaese; et al. (Ecology, 2026)
Quantifying animal movements is necessary for answering a wide array of research questions in ecology and conservation biology. Consequently, ecologists have made considerable efforts to identify the best way to estimate an animal's home range, and many methods of estimating home ranges have arisen over the past half a century. Most of these methods fall into two distinct categories of estimators that have only recently been described in statistical detail: those that measure range distributions (methods such as kernel density estimation that quantify the long‐run behavior of a movement process that features restricted space use) and those that measure occurrence distributions (methods such as Brownian bridge movement models and the Correlated Random Walk Library that quantify uncertainty in an animal movement path during a specific period of observation). In this paper, we use theory, simulations, and empirical analysis to demonstrate the importance of appropriately using these two categories of distributions and their estimators. Conflating range and occurrence distributions can have serious consequences for ecological inference and conservation practice. For example, in most situations, home ranges estimated using estimators of occurrence distributions are too small, and this problem is exacerbated by ongoing improvements in tracking technology that enable more frequent and more accurate data on animal movements. We encourage researchers to use estimators of range distributions to quantify home ranges and estimators of occurrence distributions to answer other questions in movement ecology, such as when and where an animal crossed a linear feature, visited a location of interest, or interacted with other animals.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Shifts in suitability of pinyon-juniper communities: A climate adaptation framework for range-wide management of arid woodland resources - Adam Noel; Daniel R. Schlaepfer; Ian P. Barrett; Michael C. Duniway; Jodi Norris; Chris T. Domschke; Brad J. Butterfield; Megan C. Swan; Kim Hartwig; Michele R. Crist; John B. Bradford (Forest Ecology and Management, 2025)

Ancient Introgression Explains Mitochondrial Genome Capture and Mitonuclear Discordance Among South American Collared Tropidurus Lizards - Matheus M. A. Salles; André L. G. Carvalho; Adam D. Leaché; Nicolas Martinez; Frederick Bauer; Martha Motte; Viviana Espínola; Miguel T. Rodrigues; Carla Piantoni; Marcio R. Pie; André Olivotto; Guarino R. Colli; et al. (Molecular Ecology, 2025)
Mitonuclear discordance—evolutionary discrepancies between mitochondrial and nuclear DNA phylogenies—can arise from various factors, including introgression, incomplete lineage sorting, recent or ancient demographic fluctuations, sex‐biased dispersal asymmetries, among others. Understanding this phenomenon is crucial for accurately reconstructing evolutionary histories, as failing to account for discordance can lead to misinterpretations of species boundaries, phylogenetic relationships, and historical biogeographic patterns. We investigate the evolutionary drivers of mitonuclear discordance in the Tropidurus spinulosus species group, which contains nine species of lizards inhabiting open tropical and subtropical environments in South America. Using a combination of population genetic and phylogenomic approaches applied to mitochondrial and nuclear data, we identified different instances of gene flow that occurred in ancestral lineages of extant species. Our results point to a complex evolutionary history marked by prolonged isolation between species, demographic fluctuations, and potential episodes of secondary contact with genetic admixture. These conditions likely facilitated mitochondrial genome capture while diluting signals of nuclear introgression. Furthermore, we found no strong evidence supporting incomplete lineage sorting or natural selection as primary drivers of the observed mitonuclear discordance. Therefore, the unveiled patterns are most consistent with neutral demographic processes, coupled with ancient mitochondrial introgression, as the main factors underlying the mismatch between nuclear and mitochondrial phylogenies in this system. Future research could further explore the role of other demographic processes, such as asymmetric sex‐biased dispersal, in shaping these complex evolutionary patterns.

One for all and all for one health: Harmonizing SARS-CoV-2 wastewater surveillance results across a laboratory network - Alex H.S. Chik; Christopher Adam; Jane J.Y. Ho; Taylor Aris; Eric J. Arts; R. Stephen Brown; David Bulir; Ryland Corchis-Scott; Christopher T. DeGroot; Robert Delatolla; Philip Dennis; Hadi A. Dhiyebi; et al. (Science of The Total Environment, 2025)

Comparing the Predictive Value of the Dietary Ketogenic Ratio and Healthy Eating Index for Glycemic Outcomes in People with Type 2 Diabetes on a Well-formulated Ketogenic Diet - A. Zoller; R. Adams; C. Roberts; S. Athinarayanan; B. Volk; H. Willis (Journal of the Academy of Nutrition and Dietetics, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Air pollution exposures and adverse childhood experiences in relation to sleep health in middle childhood - Jonika B. Hash; Logan C. Dearborn; Christine T. Loftus; Catherine J. Karr; Adam A. Szpiro; Emily S. Barrett; Kaja Z. LeWinn; Ruby Nguyen; Paul E. Moore; Brent Collett; Amanda N. Noroña-Zhou; Nicole R. Bush; et al. (International Journal of Hygiene and Environmental Health, 2025)

Associations of alternative cannabis product use and poly-use with subsequent illicit drug use initiation during adolescence - Jessica L. Braymiller; Kira E. Riehm; Madeline Meier; Evan A. Krueger; Jennifer B. Unger; Jessica L. Barrington-Trimis; Junhan Cho; H. Isabella Lanza; Danielle R. Madden; Afton Kechter; Adam M. Leventhal (Psychopharmacology, 2025)
Rationale Specific cannabis products may differentially increase risk of initiating non-cannabis illicit drug use during adolescence. Objective To determine whether ever- and poly-use of smoked, vaporized, edible, concentrate, or blunt cannabis products are associated with subsequent initiation of non-cannabis illicit drug use. Methods High school students from Los Angeles completed in-classroom surveys. The analytic sample ( N = 2163; 53.9% female; 43.5% Hispanic/Latino; baseline M age = 17.1 years) included students who reported never using illicit drugs at baseline (spring, 11th grade) and provided data at follow-up (fall and spring, 12th grade). Logistic regression models assessed associations between use of smoked, vaporized, edible, concentrate, and blunt cannabis at baseline (yes/no for each product) and any non-cannabis illicit drug use initiation—including cocaine, methamphetamine, psychedelics, ecstasy, heroin, prescription opioids, or benzodiazepines—at follow-up. Results Among those who never used non-cannabis illicit drugs at baseline, ever cannabis use varied by cannabis product (smoked = 25.8%, edible = 17.5%, vaporized = 8.4%, concentrates = 3.9%, and blunts = 18.2%) and patterns of use (single product use = 8.2% and poly-product use = 21.8%). After adjustment for baseline covariates, odds of illicit drug use at follow-up were largest for baseline ever users of concentrates (aOR [95% CI] = 5.74[3.16–10.43]), followed by vaporized (aOR [95% CI] = 3.11 [2.41–4.01]), edibles (aOR [95% CI] = 3.43 [2.32–5.08]), blunts (aOR [95% CI] = 2.66[1.60–4.41]), and smoked (aOR [95% CI] = 2.57 [1.64–4.02]) cannabis. Ever use of a single product (aOR [95% CI] = 2.34 [1.26–4.34]) or 2 + products (aOR [95% CI] = 3.82 [2.73–5.35]) were also associated with greater odds of illicit drug initiation. Conclusions For each of five different cannabis products, cannabis use was associated with greater odds of subsequent illicit drug use initiation, especially for cannabis concentrate and poly-product use.

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Conserving cross-realm coastal biodiversity when real-world planning and implementation processes split the land and sea - Linda R. Harris; Lara van Niekerk; Stephen D. Holness; Kerry J. Sink; Andrew L. Skowno; Anisha Dayaram; Heidi van Deventer; Nancy Job; Stephen J. Lamberth; Janine B. Adams; Jacqueline L. Raw; Taryn Riddin; et al. (Ocean & Coastal Management, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Management and Natural Regeneration in Multiple Ponderosa Pine Forests of the Southwestern United States - Matthew D. Petrie; Robert M. Hubbard; John B. Bradford; Tom E. Kolb; Adam Noel; Daniel R. Schlaepfer; Marisa A. Bowen; Lloyd R. Fuller; W. Keith Moser (Forest Science, 2025)

The reliability of functional and systemic markers of muscle damage in response to a flywheel squat protocol - Trevor J. Dufner; Alexandria D. Iacono; Jacob R. Wheeler; Natalia B. Lanier; Gabrielle Gillespie; Amalia E. Proper; Jessica M. Moon; Sarah K. Fretti; Jeffrey R. Stout; Marco Beato; Adam J. Wells (European Journal of Applied Physiology, 2025)

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Community Outreach, Engagement, and Mentoring Program for Underrepresented Scholars in Cancer Health Disparities - Lorna H. McNeill; Cassandra L. Harris; Terrence R. Adams; Berta R. Salazar; Crystal L. Roberson; Leonetta B. Thompson; Kamisha H. Escoto; Kayce D. Solari Williams; Shine Chang; Tzuan A. Chen; Birnur Buzcu-Guven; Lorraine R. Reitzel (Journal of Cancer Education, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Synchrotron X-ray Fluorescence Microscopy Reveals Trace Elemental Indicators of Life History in Marsupial Teeth - William M. G. Parker; Justin W. Adams; David P. Hocking; Erich M. G. Fitzgerald; Geoff Shaw; Marilyn B. Renfree; Alistair R. Evans (Biological Trace Element Research, 2025)
As teeth develop, their mineralised composition is a bio-recorder of diet, environment, and growth. High-resolution elemental mapping provides a tool to reveal records of life history within teeth. The relative concentrations of a range of trace elements change between in utero development, birth, and weaning in eutherian mammals. Marsupials, however, have a different mode of development: altricial birth and growth within the pouch facilitated by compositional transitions in milk. How these differences alter patterns of elemental mineralisation and become recorded in marsupial teeth is previously unknown. This study analyses the distribution of calcium (major element), zinc (actively incorporated trace element), and strontium (passively incorporated trace element) in the teeth of five species of diprotodontian marsupial using synchrotron X-ray fluorescence microscopy. We find that the diprotodontian lower incisor concatenates elemental variation from across the molariform dentition, preserving a prolonged record of life history in four of the five species. Patterns of elemental incorporation in enamel, dentine, and cementum are presented, with Ca, Zn, and Sr having differing distributions. Zn accretion indicates a role in mineralisation and/or prevention of tooth degradation. Zn also demarcates incremental cementum lines. Sr is shown to be passively incorporated into marsupial teeth, with increasing Sr concentration in milk recorded in dental tissues formed contemporaneously. Older individuals have oscillatory signals in Sr that appear linked to seasonality. These findings highlight some similarities between eutherian and marsupial trace element incorporation, particularly in the distribution of Zn. Sr signals in marsupial teeth record key aspects of life history.

Minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA) - Monita Sharma; Erin Huber; Emma Arnesdotter; Holger P. Behrsing; Adam Bettmann; David Brandwein; Samuel Constant; Rahul Date; Abhay Deshpande; Eric Fabian; Amit Gupta; Robert Gutierrez; et al. (Archives of Toxicology, 2025)
Standard information reporting helps to ensure that assay conditions and data are consistently reported and to facilitate inter-laboratory comparisons. Here, we present recommendations on minimum information for reporting on the TEER (trans-epithelial/endothelial electrical resistance) assay (MIRTA). The TEER assay is extensively used to evaluate the health of an epithelial/endothelial cell culture model and as an indicator of the potential toxicity of a test substance. This publication is the result of an international collaboration─called the RespTox (Respiratory Toxicity) Collaborative─through which twelve laboratories shared their protocols for assessing the barrier function of respiratory epithelial cells using the TEER assay following exposure to substances. The protocols from each laboratory were reviewed to identify general steps for performing the TEER assay, interlaboratory differences between steps, the rationale for differences, whether these differences impact results or cross-laboratory comparisons between TEER measurements. While the MIRTA recommendations are focused on respiratory epithelial cell systems, these recommendations can be adapted for other cell systems that form barriers. The use of these recommendations will support data transparency and reproducibility, reduce challenges in data interpretation, enable cross-laboratory comparisons, help assess study quality, and facilitate the incorporation of the TEER assay into national and international testing guidance.

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Genome-wide association study reveals effect of nsSNPs on candidate genes in rice during iron deficiency - Siddharth Panda; Annamalai Anandan; K. Mohamed Shafi; Mahantesha B. N. Naika; R. Sowdhamini; G. Vanishree; Sutapa Sarkar; Anthony J. Travis; Gareth J. Norton; Adam H. Price (Functional & Integrative Genomics, 2024)

Limited effects of thinning on laminated root rot induced tree mortality in Douglas-fir forests of the Pacific Northwest, USA - Shawn B. McMurtrey; David N. Showalter; Adam R. Carson; Michael McWilliams; (Irene) Blakey Lockman; Everett M. Hansen; Jared M. LeBoldus (Forest Ecology and Management, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Female Collegiate Athletes’ Concussion Characteristics and Recovery Patterns: A Report from the NCAA-DoD CARE Consortium - Landon B. Lempke; Jaclyn B. Caccese; Reid A. Syrydiuk; Thomas A. Buckley; Sara P. D. Chrisman; James R. Clugston; James T. Eckner; Elsa Ermer; Carrie Esopenko; Divya Jain; Louise A. Kelly; Allyssa K. Memmini; et al. (Annals of Biomedical Engineering, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

LGBTQ+ cancer: priority or lip service? A qualitative content analysis of LGBTQ+ considerations in U.S. state, jurisdiction, and tribal comprehensive cancer control plans - Austin R. Waters; Madeline H. Bono; Mayuko Ito Fukunaga; Manal Masud; Megan A. Mullins; Ryan Suk; Meghan C. O’Leary; Swann A. Adams; Renée M. Ferrari; Mary Wangen; Olufeyisayo O. Odebunmi; Sarah H. Nash; et al. (Cancer Causes & Control, 2024)

Neutralizing RGMa with Elezanumab Promotes Cerebroprotection and Recovery in Rabbit Middle Cerebral Artery Occlusion - Peer B. Jacobson; Andrea Mothe; Aharon Levy; Michael Krakovsky; Bradley A. Hooker; Xiaomeng Zhang; Jennifer Mollon; Yulia Mordashova; Mathias Droescher; Sabine Weiss; Stefan Barghorn; Ingeborg Dreher; et al. (Translational Stroke Research, 2024)
Repulsive guidance molecule A (RGMa) is an inhibitor of neuronal growth and survival which is upregulated in the damaged central nervous system following acute spinal cord injury (SCI), traumatic brain injury, acute ischemic stroke (AIS), and other neuropathological conditions. Neutralization of RGMa is neuroprotective and promotes neuroplasticity in several preclinical models of neurodegeneration and injury including multiple sclerosis, AIS, and SCI. Given the limitations of current treatments for AIS due to narrow time windows to intervention (TTI), and restrictive patient selection criteria, there is significant unmet need for therapeutic agents that enable tissue survival and repair following acute ischemic damage for a broader population of stroke patients. In this preclinical study, we evaluated whether elezanumab, a human anti-RGMa monoclonal antibody, could improve neuromotor function and modulate neuroinflammatory cell activation following AIS with delayed intervention times up to 24 h using a rabbit embolic permanent middle cerebral artery occlusion model (pMCAO). In two replicate 28-day pMCAO studies, weekly intravenous infusions of elezanumab, over a range of doses and TTIs of 6 and 24 h after stroke, significantly improved neuromotor function in both pMCAO studies when first administered 6 h after stroke. All elezanumab treatment groups, including the 24 h TTI group, had significantly less neuroinflammation as assessed by microglial and astrocyte activation. The novel mechanism of action and potential for expanding TTI in human AIS make elezanumab distinct from current acute reperfusion therapies, and support evaluation in clinical trials of acute CNS damage to determine optimal dose and TTI in humans. Graphical Abstract A: Ramified/resting astrocytes and microglia in a normal, uninjured rabbit brain. B: Rabbit pMCAO brain illustrating lesion on right side of brain (red), surrounded by penumbra (pink) during acute phase post stroke, with minimal injury to left brain hemisphere. Penumbra characterized by activated astrocytes and microglia (region in crosshair within circle), with upregulation of free and bound RGMa. C: Elezanumab binds to both free and bound RGMa, preventing full activation of astrocytes and microglia. D: Elezanumab is efficacious in rabbit pMCAO with a 4 × larger TTI window vs. tPA (6 vs. 1.5 h, respectively). In human AIS, tPA is approved for a TTI of 3-4.5 h. Elezanumab is currently being evaluated in a clinical Ph2 study of AIS to determine the optimal dose and TTI (NCT04309474).

Impact of Various 10-min Cooling Breaks on Internal Body Temperature Responses During Subsequent Intermittent Exercise in the Heat: Application to Tennis - Ayami Yoshihara; Jillian R. O’Neil; Amir M. Defino; Fredy A. Celedon; Ellamarie B. Fox; Robert A. Huggins; Neal R. Glaviano; William M. Adams; Douglas J. Casa; Rebecca L. Stearns (Journal of Science in Sport and Exercise, 2024)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Prenatal exposure to polycyclic aromatic hydrocarbons and executive functions at school age: Results from a combined cohort study - Yu Ni; Adam A. Szpiro; Christine T. Loftus; Tomomi Workman; Alexis Sullivan; Erin R. Wallace; Anne M. Riederer; Drew B. Day; Laura E. Murphy; Ruby H.N. Nguyen; Sheela Sathyanarayana; Emily S. Barrett; et al. (International Journal of Hygiene and Environmental Health, 2024)

Root exudation links root traits to soil functioning in agroecosystems - Adam C. von Haden; William C. Eddy; Mark. B. Burnham; Edward R. Brzostek; Wendy H. Yang; Evan H. DeLucia (Plant and Soil, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Development and validation of RP-HPLC method for estimation of quercetin present in hydro alcoholic extract of Erigeron bonariensis Linn. - Vishal B. Mahanur; Rahul R. Rajge; Sukriti Vishwas; M.V.N.L. Chaitanya; Salahuddin; Rashmi Mishra; Narendra Kumar Pandey; Saurabh Singh; Dileep Singh Baghel; Gaurav Gupta; Trudi Collet; Oluwafemi Omoniyi Oguntibeju; et al. (South African Journal of Botany, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

The common marmoset as a translational model of age-related osteoarthritis - Dennis M. Minton; Aditya R. Ailiani; Michael D. K. Focht; Mariana E. Kersh; Angela J. Marolf; Kelly S. Santangelo; Adam B. Salmon; Adam R. Konopka (GeroScience, 2024)

Integrative demographic modelling reduces uncertainty in estimated rates of species' historical range shifts - Antonio R. Castilla; Alissa Brown; Sean Hoban; Everett Andrew Abhainn; John D. Robinson; Jeanne Romero‐Severson; Adam B. Smith; Allan E. Strand; John R. Tipton; Andria Dawson (Journal of Biogeography, 2024)
Aim Biogeographers have used three primary data types to examine shifts in tree ranges in response to past climate change: fossil pollen, genetic data and contemporary occurrences. Although recent efforts have explored formal integration of these types of data, we have limited understanding of how integration affects estimates of range shift rates and their uncertainty. We compared estimates of biotic velocity (i.e. rate of species' range shifts) using each data type independently to estimates obtained using integrated models. Location Eastern North America. Taxon Fraxinus pennsylvanica Marshall (green ash). Methods Using fossil pollen, genomic data and modern occurrence data, we estimated biotic velocities directly from 24 species distribution models (SDMs) and 200 pollen surfaces created with a novel Bayesian spatio‐temporal model. We compared biotic velocity from these analyses to estimates based on coupled demographic‐coalescent simulations and Approximate Bayesian Computation that combined fossil pollen and SDMs with population genomic data collected across the F. pennsylvanica range. Results Patterns and magnitude of biotic velocity over time varied by the method used to estimate past range dynamics. Estimates based on fossil pollen yielded the highest rates of range movement. Overall, integrating genetic data with other data types in our simulation‐based framework reduced apparent uncertainty in biotic velocity estimates and resulted in greater similarity in estimates between SDM‐ and pollen‐integrated analyses. Main Conclusions By reducing uncertainty in our assessments of range shifts, integration of data types improves our understanding of the past distribution of species. Based on these results, we propose further steps to reach the integration of these three lines of biogeographical evidence into a unified analytical framework.

Long-term ozone exposure and lung function in middle childhood - Marnie F. Hazlehurst; Logan C. Dearborn; Allison R. Sherris; Christine T. Loftus; Margaret A. Adgent; Adam A. Szpiro; Yu Ni; Drew B. Day; Joel D. Kaufman; Neeta Thakur; Rosalind J. Wright; Sheela Sathyanarayana; et al. (Environmental Research, 2024)

Canary in the forest?—Tree mortality and canopy dieback of western redcedar linked to drier and warmer summers - R. A. Andrus; L. R. Peach; A. R. Cinquini; B. Mills; J. T. Yusi; C. Buhl; M. Fischer; B. A. Goodrich; J. M. Hulbert; A. Holz; A. J. H. Meddens; K. B. Moffett; et al. (Journal of Biogeography, 2024)
Aim Forest dieback is increasing from unfavourable climate conditions. Western redcedar (WRC)—a culturally, ecologically and economically important species—has recently experienced anomalously high mortality rates and partial canopy dieback. We investigated how WRC tree growth and dieback responded to climate variability and drought using tree‐ring methods. Location Pacific Northwest, USA. Taxon Western redcedar ( Thuja plicata ). Methods We collected tree cores from three tree health status groups (no canopy dieback, partial canopy dieback, and dead trees) at 11 sites in coastal (maritime climate) and interior (continental climate) WRC populations. From growth rates, we computed four growth indices that assessed the resilience to drought and estimated the year of death. Results Warmer and drier climate conditions in May/June that extended the annual July‐to‐September dry season reduced radial growth in 9 of 11 sites (1975–2020). WRC trees recovered growth to pre‐drought rates within 3 years when post‐drought climate conditions were cooler/wetter than average. However, recovery from drought was slower or absent when warmer/drier conditions occurred during the post‐drought recovery period, possibly leading to the recent and widespread mortality across the coastal population. WRC mortality was portended by 4–5 years of declining growth. Annually‐resolved mortality in coastal populations predominately occurred in 2017–2018 (80% of sampled dead trees), a period that coincided with exceedingly hot temperatures and the longest regionally dry period from May to September (1970–2020). In interior populations, mortality was dispersed among years but associated with warmer and drier conditions from August to September. Main conclusions Our findings forewarn that a warming climate and more frequent and severe summer droughts, especially in consecutive years, will likely increase the vulnerability of WRC to canopy dieback and mortality and possibly other drought‐sensitive trees in one of the world's largest forest carbon sinks.

Thirty-five-year timber harvesting disturbance effects on composition and biomass of tupelo-cypress (Nyssa-Taxodium) forested wetlands, southwest Alabama, USA - Cora Every; W. Michael Aust; David R. Carter; T. Adam Coates; Erik B. Schilling (Wetlands, 2023)

Managing the Seemingly Unmanageable: Water Quality and Phytoplankton Dynamics in a Heavily Urbanised Low-Inflow Estuary - Daniel A. Lemley; Lucienne R. D. Human; Gavin M. Rishworth; Emily Whitfield; Janine B. Adams (Estuaries and Coasts, 2023)

The special sauce of the Cancer Prevention and Control Research Network: 20 years of lessons learned in developing the evidence base, building community capacity, and translating research into practice - Stephanie B. Wheeler; Rebecca J. Lee; Alexa L. Young; Adam Dodd; Charlotte Ellis; Bryan J. Weiner; Kurt M. Ribisl; Prajakta Adsul; Sarah A. Birken; María E. Fernández; Peggy A. Hannon; James R. Hébert; et al. (Cancer Causes & Control, 2023)
Purpose The Cancer Prevention and Control Research Network (CPCRN) is a national network focused on accelerating the translation of cancer prevention and control research evidence into practice through collaborative, multicenter projects in partnership with diverse communities. From 2003 to 2022, the CPCRN included 613 members. Methods We: (1) characterize the extent and nature of collaborations through a bibliometric analysis of 20 years of Network publications; and (2) describe key features and functions of the CPCRN as related to organizational structure, productivity, impact, and focus on health equity, partnership development, and capacity building through analysis of 22 in-depth interviews and review of Network documentation. Results Searching Scopus for multicenter publications among the CPCRN members from their time of Network engagement yielded 1,074 collaborative publications involving two or more members. Both the overall number and content breadth of multicenter publications increased over time as the Network matured. Since 2004, members submitted 123 multicenter grant applications, of which 72 were funded (59%), totaling more than $77 million secured. Thematic analysis of interviews revealed that the CPCRN’s success—in terms of publication and grant productivity, as well as the breadth and depth of partnerships, subject matter expertise, and content area foci—is attributable to: (1) its people–the inclusion of members representing diverse content-area interests, multidisciplinary perspectives, and geographic contexts; (2) dedicated centralized structures and processes to enable and evaluate collaboration; and (3) focused attention to strategically adapting to change. Conclusion CPCRN’s history highlights organizational, strategic, and practical lessons learned over two decades to optimize Network collaboration for enhanced collective impact in cancer prevention and control. These insights may be useful to others seeking to leverage collaborative networks to address public health problems.

Living mulches reduce natural enemies when combined with frequent pesticide applications - T. Blake Hudson; Adam M. Alford; Tom R. Bilbo; Sean C. Boyle; Helene B. Doughty; Thomas P. Kuhar; Lorena Lopez; Kelly C. McIntyre; Allison K. Stawara; James F. Walgenbach; Courtney Walls; Carmen K. Blubaugh (Agriculture, Ecosystems & Environment, 2023)

Blazing a trail for the clinical use of rapamycin as a geroprotecTOR - Adam R. Konopka; Dudley W. Lamming; Brittany A. Grasso; Rebecca C. Marrah; Sara Decker; Neetika Garg; Yeonhee Park; Sin Yin Lim; Judith A. Simcox; Cara L. Green; Isaac Grunow; Amanjot K. Yadev; et al. (GeroScience, 2023)

Cultivation of heterotrophic Euglena gracilis: The effects of recycled media on culture growth and associations with growth regulating phytohormone profiles - Alexandra M. Kuhne; Erin N. Morrison; Tamanna Sultana; Anna B. Kisiala; Kathleen Horlock-Roberts; Adam Noble; R. J. Neil Emery (Journal of Applied Phycology, 2023)

Changes in oral health during aging in a novel non-human primate model - Parveez Ahamed Abdul-Azees; Hanzhou Wang; Yong-Hee P. Chun; Jason Pizzini; David D. Dean; Kelly R. Reveles; Milos Marinkovic; Xiao-Dong Chen; Adam B. Salmon; Chih-Ko Yeh (GeroScience, 2023)

Functional network disorganization and cognitive decline following fractionated whole-brain radiation in mice - Benjamin A. Seitzman; Francisco J. Reynoso; Timothy J. Mitchell; Annie R. Bice; Anmol Jarang; Xiaodan Wang; Cedric Mpoy; Lori Strong; Buck E. Rogers; Carla M. Yuede; Joshua B. Rubin; Stephanie M. Perkins; et al. (GeroScience, 2023)
Cognitive dysfunction following radiotherapy (RT) is one of the most common complications associated with RT delivered to the brain, but the precise mechanisms behind this dysfunction are not well understood, and to date, there are no preventative measures or effective treatments. To improve patient outcomes, a better understanding of the effects of radiation on the brain’s functional systems is required. Functional magnetic resonance imaging (fMRI) has shown promise in this regard, however, compared to neural activity, hemodynamic measures of brain function are slow and indirect. Understanding how RT acutely and chronically affects functional brain organization requires more direct examination of temporally evolving neural dynamics as they relate to cerebral hemodynamics for bridging with human studies. In order to adequately study the underlying mechanisms of RT-induced cognitive dysfunction, the development of clinically mimetic RT protocols in animal models is needed. To address these challenges, we developed a fractionated whole-brain RT protocol (3Gy/day for 10 days) and applied longitudinal wide field optical imaging (WFOI) of neural and hemodynamic brain activity at 1, 2, and 3 months post RT. At each time point, mice were subject to repeated behavioral testing across a variety of sensorimotor and cognitive domains. Disruptions in cortical neuronal and hemodynamic activity observed 1 month post RT were significantly worsened by 3 months. While broad changes were observed in functional brain organization post RT, brain regions most impacted by RT occurred within those overlapping with the mouse default mode network and other association areas similar to prior reports in human subjects. Further, significant cognitive deficits were observed following tests of novel object investigation and responses to auditory and contextual cues after fear conditioning. Our results fill a much-needed gap in understanding the effects of whole-brain RT on systems level brain organization and how RT affects neuronal versus hemodynamic signaling in the cortex. Having established a clinically-relevant injury model, future studies can examine therapeutic interventions designed to reduce neuroinflammation-based injury following RT. Given the overlap of sequelae that occur following RT with and without chemotherapy, these tools can also be easily incorporated to examine chemotherapy-related cognitive impairment.

Harnessing unexplored medicinal values of the red listed South African weed Erigeron bonariensis: From ethnobotany to biomedicine - Vishal B. Mahanur; Rahul R. Rajge; Rashmi Saxena Pal; M.V.N.L. Chaitanya; Sukriti Vishwas; Saurabh Gupta; Gaurav Gupta; Deepak Kumar; Oluwafemi Omoniyi Oguntibeju; Zia ur Rehman; Faris F. Aba Alkhayl; Vinay Thakur; et al. (South African Journal of Botany, 2023)

Parasite manipulation of host phenotypes inferred from transcriptional analyses in a trematode‐amphipod system - David M. Rand; Joaquin C. B. Nunez; Shawn Williams; Stephen Rong; John T. Burley; Kimberly B. Neil; Adam N. Spierer; Wilson McKerrow; David S. Johnson; Yevgeniy Raynes; Thomas J. Fayton; Nicholas Skvir; et al. (Molecular Ecology, 2023)
Manipulation of host phenotypes by parasites is hypothesized to be an adaptive strategy enhancing parasite transmission across hosts and generations. Characterizing the molecular mechanisms of manipulation is important to advance our understanding of host–parasite coevolution. The trematode ( Levinseniella byrdi ) is known to alter the colour and behaviour of its amphipod host ( Orchestia grillus ) presumably increasing predation of amphipods which enhances trematode transmission through its life cycle. We sampled 24 infected and 24 uninfected amphipods from a salt marsh in Massachusetts to perform differential gene expression analysis. In addition, we constructed novel genomic tools for O. grillus including a de novo genome and transcriptome. We discovered that trematode infection results in upregulation of amphipod transcripts associated with pigmentation and detection of external stimuli, and downregulation of multiple amphipod transcripts implicated in invertebrate immune responses, such as vacuolar ATPase genes. We hypothesize that suppression of immune genes and the altered expression of genes associated with coloration and behaviour may allow the trematode to persist in the amphipod and engage in further biochemical manipulation that promotes transmission. The genomic tools and transcriptomic analyses reported provide new opportunities to discover how parasites alter diverse pathways underlying host phenotypic changes in natural populations.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Where can managers effectively resist climate‐driven ecological transformation in pinyon–juniper woodlands of the US Southwest? - Adam R. Noel; Robert K. Shriver; Shelley D. Crausbay; John B. Bradford (Global Change Biology, 2023)
Pinyon–juniper (PJ) woodlands are an important component of dryland ecosystems across the US West and are potentially susceptible to ecological transformation. However, predicting woodland futures is complicated by species‐specific strategies for persisting and reproducing under drought conditions, uncertainty in future climate, and limitations to inferring demographic rates from forest inventory data. Here, we leverage new demographic models to quantify how climate change is expected to alter population demographics in five PJ tree species in the US West and place our results in the context of a climate adaptation framework to resist, accept, or direct ecological transformation. Two of five study species, Pinus edulis and Juniperus monosperma , are projected to experience population declines, driven by both rising mortality and decreasing recruitment rates. These declines are reasonably consistent across various climate futures, and the magnitude of uncertainty in population growth due to future climate is less than uncertainty due to how demographic rates will respond to changing climate. We assess the effectiveness of management to reduce tree density and mitigate competition, and use the results to classify southwest woodlands into areas where transformation is (a) unlikely and can be passively resisted, (b) likely but may be resisted by active management, and (c) likely unavoidable, requiring managers to accept or direct the trajectory. Population declines are projected to promote ecological transformation in the warmer and drier PJ communities of the southwest, encompassing 37.1%–81.1% of our sites, depending on future climate scenarios. Less than 20% of sites expected to transform away from PJ have potential to retain existing tree composition by density reduction. Our results inform where this adaptation strategy could successfully resist ecological transformation in coming decades and allow for a portfolio design approach across the geographic range of PJ woodlands.

Pan-primate studies of age and sex - Steve Horvath; Amin Haghani; Joseph A. Zoller; Ake T. Lu; Jason Ernst; Matteo Pellegrini; Anna J. Jasinska; Julie A. Mattison; Adam B. Salmon; Ken Raj; Markus Horvath; Kimberly C. Paul; et al. (GeroScience, 2023)
Age and sex have a profound effect on cytosine methylation levels in humans and many other species. Here we analyzed DNA methylation profiles of 2400 tissues derived from 37 primate species including 11 haplorhine species (baboons, marmosets, vervets, rhesus macaque, chimpanzees, gorillas, orangutan, humans) and 26 strepsirrhine species (suborders Lemuriformes and Lorisiformes). From these we present here, pan-primate epigenetic clocks which are highly accurate for all primates including humans (age correlation R = 0.98). We also carried out in-depth analysis of baboon DNA methylation profiles and generated five epigenetic clocks for baboons (Olive-yellow baboon hybrid), one of which, the pan-tissue epigenetic clock, was trained on seven tissue types (fetal cerebral cortex, adult cerebral cortex, cerebellum, adipose, heart, liver, and skeletal muscle) with ages ranging from late fetal life to 22.8 years of age. Using the primate data, we characterize the effect of age and sex on individual cytosines in highly conserved regions. We identify 11 sex-related CpGs on autosomes near genes ( POU3F2, CDYL, MYCL, FBXL4, ZC3H10, ZXDC, RRAS, FAM217A, RBM39, GRIA2, UHRF2 ). Low overlap can be observed between age- and sex-related CpGs. Overall, this study advances our understanding of conserved age- and sex-related epigenetic changes in primates, and provides biomarkers of aging for all primates.

A Global Review of Catch Efficiencies of Towed Fishing Gears Targeting Scallops - Adam J. Delargy; Lynda Blackadder; Isobel Bloor; Carrie McMinn; David B. Rudders; Claire L. Szostek; Helen Dobby; Mervi Kangas; Bryce D. Stewart; James R. Williams; Kevin D.E. Stokesbury (Reviews in Fisheries Science & Aquaculture, 2023)

Age, Growth and Maturity of the Bonnethead Sphyrna tiburo in the U.S. Gulf of Mexico - Bryan S. Frazier; Elizabeth A. Vinyard; Andrew T. Fields; William B. Driggers; R. Dean Grubbs; Douglas H. Adams; J. Marcus Drymon; Jayne M. Gardiner; Jill M. Hendon; Eric Hoffmayer; Robert E. Hueter; R. J. David Wells; et al. (Environmental Biology of Fishes, 2023)

Machine Learning–Based Identification of Target Groups for Thrombectomy in Acute Stroke - Fanny Quandt; Fabian Flottmann; Vince I. Madai; Anna Alegiani; Clemens Küpper; Lars Kellert; Adam Hilbert; Dietmar Frey; Thomas Liebig; Jens Fiehler; Mayank Goyal; Jeffrey L. Saver; et al. (Translational Stroke Research, 2023)
Whether endovascular thrombectomy (EVT) improves functional outcome in patients with large-vessel occlusion (LVO) stroke that do not comply with inclusion criteria of randomized controlled trials (RCTs) but that are considered for EVT in clinical practice is uncertain. We aimed to systematically identify patients with LVO stroke underrepresented in RCTs who might benefit from EVT. Following the premises that (i) patients without reperfusion after EVT represent a non-treated control group and (ii) the level of reperfusion affects outcome in patients with benefit from EVT but not in patients without treatment benefit, we systematically assessed the importance of reperfusion level on functional outcome prediction using machine learning in patients with LVO stroke treated with EVT in clinical practice ( N = 5235, German-Stroke-Registry) and in patients treated with EVT or best medical management from RCTs ( N = 1488, Virtual-International-Stroke-Trials-Archive). The importance of reperfusion level on outcome prediction in an RCT-like real-world cohort equaled the importance of EVT treatment allocation for outcome prediction in RCT data and was higher compared to an unselected real-world population. The importance of reperfusion level was magnified in patient groups underrepresented in RCTs, including patients with lower NIHSS scores (0–10), M2 occlusions, and lower ASPECTS (0–5 and 6–8). Reperfusion level was equally important in patients with vertebrobasilar as with anterior LVO stroke. The importance of reperfusion level for outcome prediction identifies patient target groups who likely benefit from EVT, including vertebrobasilar stroke patients and among patients underrepresented in RCT patients with low NIHSS scores, low ASPECTS, and M2 occlusions.

Implementation During a Pandemic: Findings, Successes, and Lessons Learned from Community Grantees - Wilhelmenia Mathias; Karen A. Nichols; Jewel Golden-Wright; Ciaran M. Fairman; Tisha M. Felder; Lauren Workman; Karen E. Wickersham; Kimberly J. Flicker; Jingxi Sheng; Samuel B. Noblet; Swann Arp Adams; Jan M. Eberth; et al. (Journal of Cancer Education, 2023)

Long-term exposure to ambient particulate matter and stroke etiology: Results from the Women's Health Initiative - Erin R. Kulick; Melissa N. Eliot; Adam A. Szpiro; Brent A. Coull; Lesley F. Tinker; Charles B. Eaton; Eric A. Whitsel; James D. Stewart; Joel D. Kaufman; Gregory A. Wellenius (Environmental Research, 2023)

A Systematic Review of the Genetic Predisposition to Injury in Football - Alexander B. T. McAuley; David C. Hughes; Loukia G. Tsaprouni; Ian Varley; Bruce Suraci; Thomas R. Roos; Adam J. Herbert; Daniel T. Jackson; Adam L. Kelly (Journal of Science in Sport and Exercise, 2023)
Purpose Synthesise genetic association studies investigating injury involving football players to identify which genetic variants have the most empirical evidence to date. Methods A comprehensive search of the PubMed, SPORTDiscus, and MEDLINE databases until March 11th 2022 identified 34 studies. Inclusion criteria: primary investigations, included football players, examined the association of a genetic variant with injury, and were published in English. Risk of bias was assessed using the Newcastle–Ottawa Scale. A narrative synthesis summarised results. Results There were 33 candidate gene studies and one genome-wide study, with 9642 participants across all studies (range = 43–1311; median = 227). Ninety-nine polymorphisms were assessed within 63 genes. Forty-one polymorphisms were associated with injury once. Three polymorphisms had their specific allelic associations with injury replicated twice in independent cohorts: ACTN3 (rs1815739) XX genotype was associated with an increased susceptibility to non-contact muscle injuries, ACAN (rs1516797) G allele was associated with increased susceptibility to anterior cruciate ligament (ACL) injuries, and VEGFA (rs2010963) CC genotype was associated with an increased susceptibility to ACL and ligament or tendon injuries. However, several methodological issues (e.g., small sample sizes, cohort heterogeneity, and population stratification) are prevalent that limit the reliability and external validity of findings. Conclusion At present, the evidence base supporting the integration of genetic information as a prognostic or diagnosis tool for injury risk in football is weak. Future participation of organisations in international consortia is suggested to combat the current methodological issues and subsequently improve clarity concerning the underlying genetic contribution to injury susceptibility.

The transcription regulator ATF4 is a mediator of skeletal muscle aging - Matthew J. Miller; George R. Marcotte; Nathan Basisty; Cameron Wehrfritz; Zachary C. Ryan; Matthew D. Strub; Andrew T. McKeen; Jennifer I. Stern; Karl A. Nath; Blake B. Rasmussen; Andrew R. Judge; Birgit Schilling; et al. (GeroScience, 2023)
Aging slowly erodes skeletal muscle strength and mass, eventually leading to profound functional deficits and muscle atrophy. The molecular mechanisms of skeletal muscle aging are not well understood. To better understand mechanisms of muscle aging, we investigated the potential role of ATF4, a transcription regulatory protein that can rapidly promote skeletal muscle atrophy in young animals deprived of adequate nutrition or activity. To test the hypothesis that ATF4 may be involved in skeletal muscle aging, we studied fed and active muscle-specific ATF4 knockout mice (ATF4 mKO mice) at 6 months of age, when wild-type mice have achieved peak muscle mass and function, and at 22 months of age, when wild-type mice have begun to manifest age-related muscle atrophy and weakness. We found that 6-month-old ATF4 mKO mice develop normally and are phenotypically indistinguishable from 6-month-old littermate control mice. However, as ATF4 mKO mice become older, they exhibit significant protection from age-related declines in strength, muscle quality, exercise capacity, and muscle mass. Furthermore, ATF4 mKO muscles are protected from some of the transcriptional changes characteristic of normal muscle aging (repression of certain anabolic mRNAs and induction of certain senescence-associated mRNAs), and ATF4 mKO muscles exhibit altered turnover of several proteins with important roles in skeletal muscle structure and metabolism. Collectively, these data suggest ATF4 as an essential mediator of skeletal muscle aging and provide new insight into a degenerative process that impairs the health and quality of life of many older adults.

Fundamental insights into the effect of blending hydrogen flames with sooting biofuels - Yilong Yin; Paul R. Medwell; Adam J. Gee; Kae Ken Foo; Bassam B. Dally (Fuel, 2023)

Prenatal exposure to polycyclic aromatic hydrocarbons is not associated with behavior problems in preschool and early school-aged children: A prospective multi-cohort study - Erin R. Wallace; Erin Buth; Adam A. Szpiro; Yu Ni; Christine T. Loftus; Erin Masterson; Drew B. Day; Bob Z. Sun; Alexis Sullivan; Emily Barrett; Ruby HN. Nguyen; Morgan Robinson; et al. (Environmental Research, 2023)

Fermentative conversion of unpretreated plant biomass: A thermophilic threshold for indigenous microbial growth - Ryan G. Bing; Morgan J. Carey; Tunyaboon Laemthong; Daniel J. Willard; James R. Crosby; Daniel B. Sulis; Jack P. Wang; Michael W.W. Adams; Robert M. Kelly (Bioresource Technology, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Advancing the scholarship and practice of stakeholder engagement in working landscapes: a co-produced research agenda - Weston M. Eaton; Morey Burnham; Tahnee Robertson; J. G. Arbuckle; Kathryn J. Brasier; Mark E. Burbach; Sarah P. Church; Georgia Hart-Fredeluces; Douglas Jackson-Smith; Grace Wildermuth; Katherine N. Canfield; S. Carolina Córdova; et al. (Socio-Ecological Practice Research, 2022)
Participatory approaches to science and decision making, including stakeholder engagement, are increasingly common for managing complex socio-ecological challenges in working landscapes. However, critical questions about stakeholder engagement in this space remain. These include normative, political, and ethical questions concerning who participates, who benefits and loses, what good can be accomplished, and for what, whom, and by who. First, opportunities for addressing justice, equity, diversity, and inclusion interests through engagement, while implied in key conceptual frameworks, remain underexplored in scholarly work and collaborative practice alike. A second line of inquiry relates to research–practice gaps. While both the practice of doing engagement work and scholarly research on the efficacy of engagement is on the rise, there is little concerted interplay among ‘on-the-ground’ practitioners and scholarly researchers. This means scientific research often misses or ignores insight grounded in practical and experiential knowledge, while practitioners are disconnected from potentially useful scientific research on stakeholder engagement. A third set of questions concerns gaps in empirical understanding of the efficacy of engagement processes and includes inquiry into how different engagement contexts and process features affect a range of behavioral, cognitive, and decision-making outcomes. Because of these gaps, a cohesive and actionable research agenda for stakeholder engagement research and practice in working landscapes remains elusive. In this review article, we present a co-produced research agenda for stakeholder engagement in working landscapes. The co-production process involved professionally facilitated and iterative dialogue among a diverse and international group of over 160 scholars and practitioners through a yearlong virtual workshop series. The resulting research agenda is organized under six cross-cutting themes: (1) Justice, Equity, Diversity, and Inclusion; (2) Ethics; (3) Research and Practice; (4) Context; (5) Process; and (6) Outcomes and Measurement. This research agenda identifies critical research needs and opportunities relevant for researchers, practitioners, and policymakers alike. We argue that addressing these research opportunities is necessary to advance knowledge and practice of stakeholder engagement and to support more just and effective engagement processes in working landscapes.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Using Biological Responses to Monitor Freshwater Post-Spill Conditions over 3 years in Blacktail Creek, North Dakota, USA - Aїda M. Farag; David D. Harper; Isabelle M. Cozzarelli; Douglas B. Kent; Adam C. Mumford; Denise M. Akob; Travis Schaeffer; Luke R. Iwanowicz (Archives of Environmental Contamination and Toxicology, 2022)

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Physical characteristics of northern forested lakes predict sensitivity to climate change - Mark B. Edlund; Joy M. Ramstack Hobbs; Adam J. Heathcote; Daniel R. Engstrom; Jasmine E. Saros; Kristin E. Strock; William O. Hobbs; Norman A. Andresen; David D. VanderMeulen (Hydrobiologia, 2022)
Evidence suggests that boreal-lake ecosystems are changing rapidly, but with variable ecological responses, due to climate warming. Paleolimnological analysis of 27 undeveloped northern forested lakes showed significant and potentially climate-mediated shifts in diatom communities and increased carbon and biogenic silica burial. We hypothesize the sensitivity of northern forested lakes to climate change will vary along two physical gradients: one reflecting direct, in-lake climate effects (propensity to thermally stratify), the other reflecting indirect watershed effects (watershed to lake-surface area ratio). We focus on the historical response of algal communities to test our two-dimensional sensitivity framework. Historical algal response was summarized by measures of diatom community turnover, changes in species and diagnostic species groups, and measures of siliceous algal and overall primary production (biogenic silica, carbon burial). Measures of algal production increased across all lake types, with carbon burial proportionately higher in polymictic lakes. Greater diatom community change occurred in deep, stratified lakes with smaller watersheds, whereas diatom species groups showed variable responses along our two-dimensional sensitivity framework. Physical characteristics of lakes and watersheds could serve as predictors of sensitivity to climate change based on paleo-indicators that are mechanistically linked to direct and indirect limnological effects of climate change.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Recreational and occupational physical activity in relation to prostate cancer aggressiveness: the North Carolina-Louisiana Prostate Cancer Project (PCaP) - Susan E. Steck; L. Joseph Su; Samuel O. Antwi; Bonny B. Morris; Brittany Crawford; Swann Arp Adams; James R. Hebert; Elizabeth T. H. Fontham; Jeannette T. Bensen; James L. Mohler; Lenore Arab (Cancer Causes & Control, 2022)

HIV-related drivers of sexual compulsivity and sexuality in sexual minority men who use methamphetamine - Hema R. Kondur; Tae K. Lee; Roger McIntosh; Hetta Gouse; Robert Paul; Christian Grov; Dietmar Fuchs; Walter Gómez; Samantha E. Dilworth; Torsten B. Neilands; Adam W. Carrico (Journal of NeuroVirology, 2022)

Is Neuroscience FAIR? A Call for Collaborative Standardisation of Neuroscience Data - Jean-Baptiste Poline; David N. Kennedy; Friedrich T. Sommer; Giorgio A. Ascoli; David C. Van Essen; Adam R. Ferguson; Jeffrey S. Grethe; Michael J. Hawrylycz; Paul M. Thompson; Russell A. Poldrack; Satrajit S. Ghosh; David B. Keator; et al. (Neuroinformatics, 2022)
In this perspective article, we consider the critical issue of data and other research object standardisation and, specifically, how international collaboration, and organizations such as the International Neuroinformatics Coordinating Facility (INCF) can encourage that emerging neuroscience data be Findable, Accessible, Interoperable, and Reusable (FAIR) . As neuroscientists engaged in the sharing and integration of multi-modal and multiscale data, we see the current insufficiency of standards as a major impediment in the Interoperability and Reusability of research results. We call for increased international collaborative standardisation of neuroscience data to foster integration and efficient reuse of research objects.

Genetic Testing in Professional Football: Perspectives of Key Stakeholders - Alexander B. T. McAuley; David C. Hughes; Loukia G. Tsaprouni; Ian Varley; Bruce Suraci; Thomas R. Roos; Adam J. Herbert; Adam L. Kelly (Journal of Science in Sport and Exercise, 2022)
Purpose Genetic research in football is currently in it’s infancy but is growing rapidly. However, the practical application of genetic testing in football and the views concerning its use are unknown. Thus, the purpose of this study was to assess the current practical application of genetic testing in professional football and provide an insight into the perspectives of key stakeholders (i.e., coaches, practitioners, players). Methods In total, 122 participants completed an online anonymous survey. This consisted of 21 multiple choice and Likert scale questions, with the option of providing an explanation for each response. Results Findings revealed genetic testing is rarely utilised by key stakeholders (10%) or their respective organisations (14%). However, three quarters (75%) had the opinion that genetic testing will have great utility in the future. The majority (72%) believed genetic testing should be used for athlete development and injury risk, whilst 35% believed that genetic testing should be utilised for talent identification purposes. However, most key stakeholders viewed their own (89%) and their colleagues’ (79%) knowledge related to genetic testing as insufficient; mainly due to ineffective current communication methods (91%). Most believed educational workshops are required (71%), whilst nearly all (91%) were interested in developing their expertise on the utility of genetic testing. Conclusion Genetic testing is rarely used within professional football, although key stakeholders anticipate that it will be utilised more in the future. As such, educational support may prove valuable in improving key stakeholder knowledge and the practical application of genetic testing in professional football.

Corrigendum to: Leveraging Administrative Capacity to Manage Landscape-Scale, Cross-Boundary Disturbance in the Black Hills: What Roles for Federal, State, Local, and Non-Governmental Partners? - M M Steen-Adams; J B Abrams; H R Huber-Stearns; C Bone; C Moseley (Journal of Forestry, 2022)

Leveraging Administrative Capacity to Manage Landscape-Scale, Cross-Boundary Disturbance in the Black Hills: What Roles for Federal, State, Local, and Nongovernmental Partners? - M M Steen-Adams; J B Abrams; H R Huber-Stearns; C Bone; C Moseley (Journal of Forestry, 2022)
Public land management agencies, such as the USDA Forest Service (USFS), confront challenges in leveraging limited administrative capacity to effectively manage landscape-scale, cross-boundary disturbances. Using case study methods, we investigated the ~1996–2016 outbreak of mountain pine beetle (Dendroctonus ponderosae Hopkins) in the Black Hills, a 1.5 million acre region in South Dakota and Wyoming. We identified four practices that can promote the leveraging of administrative capacity: (1) establishing multilevel governance networks; (2) performing both distinct and shared (“redundant”) partner roles; (3) maximizing the collaborative toolbox: drawing upon the variety of policy tools (older, newer) and modes of use (conventional, experimental); and (4) engaging a multilevel, multiorganizational network, with attention to the ways that a variety of network linkages can deploy a variety of policy tool types. This case demonstrates how the government-led model of network governance can be applied to leverage administrative capacity. These findings point to strategies to promote landscape-scale, cross-boundary management.

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Rapid spatial expansion and population increase of invasive lionfish (Pterois spp.) observed on natural habitats in the northern Gulf of Mexico - Matthew D. Campbell; Adam G. Pollack; Kevin Thompson; Ted Switzer; William B. Driggers; Eric R. Hoffmayer; Sean Keenan; Chris Gardner; David Hanisko; Kevin R. Rademacher; Kate Overly (Biological Invasions, 2022)

How Do African-American Community Members’ Perceptions About Environmental Risks of Breast Cancer Compare with the Current State of the Science? - Brooks Yelton; Jamie R. Lead; Swann Arp Adams; Heather M. Brandt; Shibani Kulkarni; Kaleea R. Lewis; Delores Fedrick; John R. Ureda; Daniela B. Friedman (Journal of Cancer Education, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Body size and digestive system shape resource selection by ungulates: A cross‐taxa test of the forage maturation hypothesis - Saeideh Esmaeili; Brett R. Jesmer; Shannon E. Albeke; Ellen O. Aikens; Kathryn A. Schoenecker; Sarah R. B. King; Briana Abrahms; Bayarbaatar Buuveibaatar; Jeffrey L. Beck; Randall B. Boone; Francesca Cagnacci; Simon Chamaillé‐Jammes; et al. (Ecology Letters, 2021)
The forage maturation hypothesis (FMH) states that energy intake for ungulates is maximised when forage biomass is at intermediate levels. Nevertheless, metabolic allometry and different digestive systems suggest that resource selection should vary across ungulate species. By combining GPS relocations with remotely sensed data on forage characteristics and surface water, we quantified the effect of body size and digestive system in determining movements of 30 populations of hindgut fermenters (equids) and ruminants across biomes. Selection for intermediate forage biomass was negatively related to body size, regardless of digestive system. Selection for proximity to surface water was stronger for equids relative to ruminants, regardless of body size. To be more generalisable, we suggest that the FMH explicitly incorporate contingencies in body size and digestive system, with small‐bodied ruminants selecting more strongly for potential energy intake, and hindgut fermenters selecting more strongly for surface water.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Determinants of community compositional change are equally affected by global change - Meghan L. Avolio; Kimberly J. Komatsu; Scott L. Collins; Emily Grman; Sally E. Koerner; Andrew T. Tredennick; Kevin R. Wilcox; Sara Baer; Elizabeth H. Boughton; Andrea J. Britton; Bryan Foster; Laura Gough; et al. (Ecology Letters, 2021)
Global change is impacting plant community composition, but the mechanisms underlying these changes are unclear. Using a dataset of 58 global change experiments, we tested the five fundamental mechanisms of community change: changes in evenness and richness, reordering, species gains and losses. We found 71% of communities were impacted by global change treatments, and 88% of communities that were exposed to two or more global change drivers were impacted. Further, all mechanisms of change were equally likely to be affected by global change treatments—species losses and changes in richness were just as common as species gains and reordering. We also found no evidence of a progression of community changes, for example, reordering and changes in evenness did not precede species gains and losses. We demonstrate that all processes underlying plant community composition changes are equally affected by treatments and often occur simultaneously, necessitating a wholistic approach to quantifying community changes.

Chronic SSRI treatment reverses HIV-1 protein-mediated synaptodendritic damage - Adam R. Denton; Charles F. Mactutus; Almeera U. Lateef; Steven B. Harrod; Rosemarie M. Booze (Journal of NeuroVirology, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Ecotoxicity and genotoxicity assessment of losartan after UV/H2O2 and UVC/photolysis treatments - Eliane Adams; Bruno B. Neves; Liziê D. T. Prola; Marcus V. de Liz; Lucia R. R. Martins; Wanessa A. Ramsdorf; Adriane M. de Freitas (Environmental Science and Pollution Research, 2021)

Coordinating Global Multi-Site Studies of Military-Relevant Traumatic Brain Injury: Opportunities, Challenges, and Harmonization Guidelines - David F Tate; Emily L Dennis; John T Adams; Maheen M Adamson; Heather G Belanger; Erin D Bigler; Heather C Bouchard; Alexandra L Clark; Lisa M Delano-Wood; Seth G Disner; Blessen C Eapen; Carol E Franz; et al. (Brain Imaging and Behavior, 2021)

Tryptophan depletion predicts lower positive affect in sexual minority men living with HIV who use methamphetamine - Ji-Young Lee; Tiffany R. Glynn; Judith T. Moskowitz; Dietmar Fuchs; Torsten B. Neilands; Samantha E. Dilworth; Daniel J. Feaster; Allan Rodriguez; Adam W. Carrico (Journal of NeuroVirology, 2021)

Short-term neuromuscular, morphological, and architectural responses to eccentric quasi-isometric muscle actions - Dustin J. Oranchuk; André R. Nelson; Adam G. Storey; Shelley N. Diewald; John B. Cronin (European Journal of Applied Physiology, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Hurricane Sandy Effects on Coastal Marsh Elevation Change - Alice G. Yeates; James B. Grace; Jennifer H. Olker; Glenn R. Guntenspergen; Donald R. Cahoon; Susan Adamowicz; Shimon C. Anisfeld; Nels Barrett; Alice Benzecry; Linda Blum; Robert R. Christian; Joseph Grzyb; et al. (Estuaries and Coasts, 2020)

Characterization of a highly heterogeneous flysch deposit and excavation implications: case study from Auckland, New Zealand - B. Fleetwood; M. S. Brook; G. Brink; N. R. Richards; L. Adam; P. M. Black (Bulletin of Engineering Geology and the Environment, 2020)

Prescription psychostimulants for the treatment of stimulant use disorder: a systematic review and meta-analysis - Vitor S. Tardelli; Adam Bisaga; Felipe B. Arcadepani; Gilberto Gerra; Frances R. Levin; Thiago M. Fidalgo (Psychopharmacology, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Genomic evidence for gene flow between monarchs with divergent migratory phenotypes and flight performance - Venkat Talla; Amanda A. Pierce; Kandis L. Adams; Tom J. B. de Man; Sumitha Nallu; Francis X. Villablanca; Marcus R. Kronforst; Jacobus C. de Roode (Molecular Ecology, 2020)
Monarch butterflies are known for their spectacular annual migration in eastern North America, with millions of monarchs flying up to 4,500 km to overwintering sites in central Mexico. Monarchs also live west of the Rocky Mountains, where they travel shorter distances to overwinter along the Pacific Coast. It is often assumed that eastern and western monarchs form distinct evolutionary units, but genomic studies to support this notion are lacking. We used a tethered flight mill to show that migratory eastern monarchs have greater flight performance than western monarchs, consistent with their greater migratory distances. However, analysing more than 20 million SNPs in 43 monarch genomes, we found no evidence for genomic differentiation between eastern and western monarchs. Genomic analysis also showed identical and low levels of genetic diversity, and demographic analyses indicated similar effective population sizes and ongoing gene flow between eastern and western monarchs. Gene expression analysis of a subset of candidate genes during active flight revealed differential gene expression related to nonmuscular motor activity. Our results demonstrate that eastern and western monarchs maintain migratory differences despite ongoing gene flow, and suggest that migratory differences between eastern and western monarchs are not driven by select major‐effects alleles. Instead, variation in migratory distance and destination may be driven by environmentally induced differential gene expression or by many alleles of small effect.

Role of Quaternary glacial-outburst megaflood paleochannel deposits in a basalt-dominated aquifer system in the West Plains area of eastern Washington, USA - Chad J. Pritchard; David R. Gaylord; Drew B. Adams; Shawna Ernst; Michael Hermanson (Hydrogeology Journal, 2020)

Seasonal and diel patterns in activity and habitat use by brook trout (Salvelinus fontinalis) in a small Newfoundland lake - D. Cote; B. Tibble; R. A. Curry; S. Peake; B. K. Adams; K. D. Clarke; R. Perry (Environmental Biology of Fishes, 2020)
Despite the challenges winter poses to salmonids inhabiting temperate and northern environments, there are relatively few studies that evaluate the factors that influence activity and habitat use during this season, particularly for lake environments that are ice-covered. This study examines brook trout depth distribution and movement (activity and range) in relation to temperature, light, and time of day across a 17-month period in a small lake in Newfoundland, Canada. Brook trout maintained elevated diurnal activity patterns throughout the year, despite seasonal changes in temperature, shifts in depth use, and prolonged, ice-induced darkness. Despite the tendency for relatively lower activity at night, brook trout remained active nocturnally, inferring a shift in foraging modes rather than a cessation of feeding. Winter movement velocities and ranges were less than other seasons but they occupied littoral areas that overlapped extensively with spring and fall core ranges. In contrast, summer core ranges of brook trout were principally comprised of areas with cooler water in the deep portion of the lake. As water temperature increased, daytime movement velocities increased in a log-linear fashion, whereas modeled nighttime movement velocity relationships with temperature were curvilinear and included the lowest movement velocities at 2–3 °C and the highest at the extremes of the occupied temperature range. The ability of brook trout to maintain diurnal activity patterns throughout a wide spectrum of environmental conditions suggests a strong behavioral and physiological capacity to adapt to their seasonally variable environment.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Selective monoaminergic and histaminergic circuit dysregulation following long-term HIV-1 protein exposure - Adam R. Denton; Srimal A. Samaranayake; Kristin N. Kirchner; Robert F. Roscoe; Shane N. Berger; Steven B. Harrod; Charles F. Mactutus; Parastoo Hashemi; Rosemarie M. Booze (Journal of NeuroVirology, 2019)

Rise Up, Get Tested, and Live: an Arts-Based Colorectal Cancer Educational Program in a Faith-Based Setting - Daniela B. Friedman; Swann Arp Adams; Heather M. Brandt; Sue P. Heiney; James R. Hébert; John R. Ureda; Jessica S. Seel; Courtney S. Schrock; Wilhelmenia Mathias; Vivian Clark-Armstead; Reverend Vernette Dees; Reverend Perry Oliver (Journal of Cancer Education, 2019)

Kynurenine 3-Monooxygenase Activity in Human Primary Neurons and Effect on Cellular Bioenergetics Identifies New Neurotoxic Mechanisms - Gloria Castellano-Gonzalez; Kelly R. Jacobs; Emily Don; Nicholas J. Cole; Seray Adams; Chai K. Lim; David B. Lovejoy; Gilles J. Guillemin (Neurotoxicity Research, 2019)

Cellular energetics and mitochondrial uncoupling in canine aging - Justin W. Nicholatos; Timothy M. Robinette; Saurabh V.P. Tata; Jennifer D. Yordy; Adam B. Francisco; Michael Platov; Tiffany K. Yeh; Olga R. Ilkayeva; Frank K. Huynh; Maxim Dokukin; Dmytro Volkov; Michael A. Weinstein; et al. (GeroScience, 2019)

How has the quality of bonefishing changed over the past 40 years? Using local ecological knowledge to quantitatively inform population declines in the South Florida flats fishery - J. S. Rehage; R. O. Santos; E. K. N. Kroloff; J. T. Heinen; Q. Lai; B. D. Black; R. E. Boucek; A. J. Adams (Environmental Biology of Fishes, 2019)

Measuring site fidelity and homesite-to-pre-spawning site connectivity of bonefish (Albula vulpes): using mark-recapture to inform habitat conservation - R. E. Boucek; J. P. Lewis; B. D. Stewart; Z. R. Jud; E. Carey; A. J. Adams (Environmental Biology of Fishes, 2019)

Extended Water-Level Drawdowns in Dammed Rivers Enhance Fish Habitat: Environmental Pool Management in the Upper Mississippi River - A. A. Coulter; S. R. Adams; M. B. Flinn; M. R. Whiles; B. M. Burr; R. J. Sheehan; J. E. Garvey (Environmental Management, 2019)

Meta-analysis identifies mitochondrial DNA sequence variants associated with walking speed - Todd M. Manini; Thomas W. Buford; John A. Kairalla; Mary M. McDermott; Carlos A. Vaz Fragoso; Roger A. Fielding; Fang-Chi Hsu; Neil Johannsen; Stephen Kritchevsky; Tamara B. Harris; Anne B. Newman; Steven R. Cummings; et al. (GeroScience, 2018)

Real-World Variability in the Prediction of Intracranial Aneurysm Wall Shear Stress: The 2015 International Aneurysm CFD Challenge - Kristian Valen-Sendstad; Aslak W. Bergersen; Yuji Shimogonya; Leonid Goubergrits; Jan Bruening; Jordi Pallares; Salvatore Cito; Senol Piskin; Kerem Pekkan; Arjan J. Geers; Ignacio Larrabide; Saikiran Rapaka; et al. (Cardiovascular Engineering and Technology, 2018)

Ambient changes exceed treatment effects on plant species abundance in global change experiments - J. Adam Langley; Samantha K. Chapman; Kimberly J. La Pierre; Meghan Avolio; William D. Bowman; David S. Johnson; Forest Isbell; Kevin R. Wilcox; Bryan L. Foster; Mark J. Hovenden; Alan K. Knapp; Sally E. Koerner; et al. (Global Change Biology, 2018)
The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO 2 , nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2,116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes.

The role of gene flow in rapid and repeated evolution of cave‐related traits in Mexican tetra, Astyanax mexicanus - Adam Herman; Yaniv Brandvain; James Weagley; William R. Jeffery; Alex C. Keene; Thomas J. Y. Kono; Helena Bilandžija; Richard Borowsky; Luis Espinasa; Kelly O'Quin; Claudia P. Ornelas‐García; Masato Yoshizawa; et al. (Molecular Ecology, 2018)
Understanding the molecular basis of repeatedly evolved phenotypes can yield key insights into the evolutionary process. Quantifying gene flow between populations is especially important in interpreting mechanisms of repeated phenotypic evolution, and genomic analyses have revealed that admixture occurs more frequently between diverging lineages than previously thought. In this study, we resequenced 47 whole genomes of the Mexican tetra from three cave populations, two surface populations and outgroup samples. We confirmed that cave populations are polyphyletic and two Astyanax mexicanus lineages are present in our data set. The two lineages likely diverged much more recently than previous mitochondrial estimates of 5–7 mya. Divergence of cave populations from their phylogenetically closest surface population likely occurred between ~161 and 191 k generations ago. The favoured demographic model for most population pairs accounts for divergence with secondary contact and heterogeneous gene flow across the genome, and we rigorously identified gene flow among all lineages sampled. Therefore, the evolution of cave‐related traits occurred more rapidly than previously thought, and trogolomorphic traits are maintained despite gene flow with surface populations. The recency of these estimated divergence events suggests that selection may drive the evolution of cave‐derived traits, as opposed to disuse and drift. Finally, we show that a key trogolomorphic phenotype QTL is enriched for genomic regions with low divergence between caves, suggesting that regions important for cave phenotypes may be transferred between caves via gene flow. Our study shows that gene flow must be considered in studies of independent, repeated trait evolution.

A multigear protocol for sampling crayfish assemblages in Gulf of Mexico coastal streams - William R. Budnick; William E. Kelso; Susan B. Adams; Michael D. Kaller (Hydrobiologia, 2018)

Assessing phytoplankton composition and structure within micro-estuaries and micro-outlets: a community analysis approach - Tatenda Dalu; Mandla L. Magoro; Jonathan D. Tonkin; Lucienne R. D. Human; Renzo Perissinotto; Shaun H. P. Deyzel; Janine B. Adams; Alan K. Whitfield (Hydrobiologia, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Latitudinal gradients and poleward expansion of mangrove ecosystems in South Africa: 50 years after Macnae’s first assessment - N Peer; A Rajkaran; NAF Miranda; RH Taylor; B Newman; F Porri; JL Raw; SP Mbense; JB Adams; R Perissinotto (African Journal of Marine Science, 2018)

Rice ecosystem services in South-east Asia - Josef Settele; Kong Luen Heong; Ingolf Kühn; Stefan Klotz; Joachim H. Spangenberg; Gertrudo Arida; Alexis Beaurepaire; Silke Beck; Erwin Bergmeier; Benjamin Burkhard; Roland Brandl; Jesus Victor Bustamante; et al. (Paddy and Water Environment, 2018)

Alternative splicing associated with phenotypic plasticity in the bumble bee Bombus terrestris - J. Price; M. C. Harrison; R. L. Hammond; S. Adams; J. F. Gutierrez‐Marcos; E. B. Mallon (Molecular Ecology, 2018)
Phenotypic plasticity is when one genome can produce more than one phenotype. The caste system found in many social insects is an important example of plasticity. Several studies have examined gene expression in social insect developmental and caste differences. Changes in gene expression, however, are not the only source of phenotypic plasticity. Here, we investigate the role of alternative splicing in the buff‐tailed bumble bee Bombus terrestris . We found that 5,458 genes in B. terrestris (40%) express more than one isoform. Larvae have the lowest level of splicing events, followed by adults and then pupae. We found that when an isoform is expressed in a given caste in the larval stage, it tends to be expressed in all castes at the larval stage. The same is true at the pupal stage. However, we see more complicated interactions between the adult castes with reproductive females showing different isoform expression compared to nonreproductive females and male adults showing the most distinct patterns. We found 455 isoform switching genes, that is genes, where one developmental stage, sex or caste uses a specific isoform and another type uses a different isoform. Among genes displaying isoform switching are some involved in the ecdysteriod pathway, an important system in insect behaviour.

Observed trends of soil fauna in the Antarctic Dry Valleys: early signs of shifts predicted under climate change - W. S. Andriuzzi; B. J. Adams; J. E. Barrett; R. A. Virginia; D. H. Wall (Ecology, 2018)
Long‐term observations of ecological communities are necessary for generating and testing predictions of ecosystem responses to climate change. We investigated temporal trends and spatial patterns of soil fauna along similar environmental gradients in three sites of the McMurdo Dry Valleys, Antarctica, spanning two distinct climatic phases: a decadal cooling trend from the early 1990s through the austral summer of February 2001, followed by a shift to the current trend of warming summers and more frequent discrete warming events. After February 2001, we observed a decline in the dominant species (the nematode Scottnema lindsayae ) and increased abundance and expanded distribution of less common taxa (rotifers, tardigrades, and other nematode species). Such diverging responses have resulted in slightly greater evenness and spatial homogeneity of taxa. However, total abundance of soil fauna appears to be declining, as positive trends of the less common species so far have not compensated for the declining numbers of the dominant species. Interannual variation in the proportion of juveniles in the dominant species was consistent across sites, whereas trends in abundance varied more. Structural equation modeling supports the hypothesis that the observed biological trends arose from dissimilar responses by dominant and less common species to pulses of water availability resulting from enhanced ice melt. No direct effects of mean summer temperature were found, but there is evidence of indirect effects via its weak but significant positive relationship with soil moisture. Our findings show that combining an understanding of species responses to environmental change with long‐term observations in the field can provide a context for validating and refining predictions of ecological trends in the abundance and diversity of soil fauna.

Genes linked to species diversity in a sexually dimorphic communication signal in electric fish - G. Troy Smith; Melissa R. Proffitt; Adam R. Smith; Douglas B. Rusch (Journal of Comparative Physiology A, 2018)

Inhibition of the receptor for advanced glycation end-products (RAGE) protects from secondhand smoke (SHS)-induced intrauterine growth restriction IUGR in mice - Joshua B. Lewis; Camilo Mejia; Clinton Jordan; Troy D. Monson; Jared S. Bodine; Todd M. Dunaway; Kaleb M. Egbert; Adam L. Lewis; Tanner J. Wright; K. Connor Ogden; Dallin S. Broberg; Parker D. Hall; et al. (Cell and Tissue Research, 2017)

Soluble soil aluminum alters the relative uptake of mineral nitrogen forms by six mature temperate broadleaf tree species: possible implications for watershed nitrate retention - Mark B. Burnham; Jonathan R. Cumming; Mary Beth Adams; William T. Peterjohn (Oecologia, 2017)

Acute effects of heated resistance exercise in female and male power athletes - Julia R. Casadio; Adam G. Storey; Fabrice Merien; Andrew E. Kilding; James D. Cotter; Paul B. Laursen (European Journal of Applied Physiology, 2017)

Patterns and mechanisms of invasive plant impacts on North American birds: a systematic review - Scott B. Nelson; Jaime J. Coon; Courtney J. Duchardt; Jason D. Fischer; Samniqueka J. Halsey; Adam J. Kranz; Christine M. Parker; Sarah C. Schneider; Timothy M. Swartz; James R. Miller (Biological Invasions, 2017)

50 years of the International Committee on Taxonomy of Viruses: progress and prospects - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max L. Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

Application of novel analytical ultracentrifuge analysis to solutions of fungal mannans - Richard B. Gillis; Gary G. Adams; David T. M. Besong; Eva Machová; Anna Ebringerová; Arthur J. Rowe; Stephen E. Harding; Trushar R. Patel (European Biophysics Journal, 2017)

Louis M. Herman 1930–2016 - Adam A. Pack; Elia Y. K. Herman; C. Scott Baker; Gordon B. Bauer; Phillip J. Clapham; Richard C. Connor; Alison S. Craig; Paul H. Forestell; Adam S. Frankel; Giuseppe Notarbartolo di Sciara; Matthias Hoffmann‐Kuhnt; Eduardo Mercado; et al. (Marine Mammal Science, 2017)

Decontamination treatments to eliminate problem biota from macroalgal tank cultures of Osmundea pinnatifida, Palmaria palmata and Ulva lactuca - Philip D. Kerrison; Hau Nhu Le; Gail C. Twigg; Duncan R. Smallman; Rory MacPhee; Fiona A. B. Houston; Adam D. Hughes (Journal of Applied Phycology, 2016)

Resistance training intensity and volume affect changes in rate of force development in resistance-trained men - Gerald T. Mangine; Jay R. Hoffman; Ran Wang; Adam M. Gonzalez; Jeremy R. Townsend; Adam J. Wells; Adam R. Jajtner; Kyle S. Beyer; Carleigh H. Boone; Amelia A. Miramonti; Michael B. LaMonica; David H. Fukuda; et al. (European Journal of Applied Physiology, 2016)

Resistance exercise increases intramuscular NF-κb signaling in untrained males - Jeremy R. Townsend; Jeffrey R. Stout; Adam R. Jajtner; David D. Church; Kyle S. Beyer; Leonardo P. Oliveira; Michael B. La Monica; Joshua J. Riffe; Tyler W. D. Muddle; Kayla M. Baker; David H. Fukuda; Michael D. Roberts; et al. (European Journal of Applied Physiology, 2016)

Range-wide fragmentation in a threatened fish associated with post-European settlement modification in the Murray–Darling Basin, Australia - Theresa L. Cole; Michael P. Hammer; Peter J. Unmack; Peter R. Teske; Chris J. Brauer; Mark Adams; Luciano B. Beheregaray (Conservation Genetics, 2016)

Trade‐offs between savanna woody plant diversity and carbon storage in the Brazilian Cerrado - Adam F.A. Pellegrini; Jacob B. Socolar; Paul R. Elsen; Xingli Giam (Global Change Biology, 2016)
Incentivizing carbon storage can be a win‐win pathway to conserving biodiversity and mitigating climate change. In savannas, however, the situation is more complex. Promoting carbon storage through woody encroachment may reduce plant diversity of savanna endemics, even as the diversity of encroaching forest species increases. This trade‐off has important implications for the management of biodiversity and carbon in savanna habitats, but has rarely been evaluated empirically. We quantified the nature of carbon‐diversity relationships in the Brazilian Cerrado by analyzing how woody plant species richness changed with carbon storage in 206 sites across the 2.2 million km 2 region at two spatial scales. We show that total woody plant species diversity increases with carbon storage, as expected, but that the richness of endemic savanna woody plant species declines with carbon storage both at the local scale, as woody biomass accumulates within plots, and at the landscape scale, as forest replaces savanna. The sharpest trade‐offs between carbon storage and savanna diversity occurred at the early stages of carbon accumulation at the local scale but the final stages of forest encroachment at the landscape scale. Furthermore, the loss of savanna species quickens in the final stages of forest encroachment, and beyond a point, savanna species losses outpace forest species gains with increasing carbon accumulation. Our results suggest that although woody encroachment in savanna ecosystems may provide substantial carbon benefits, it comes at the rapidly accruing cost of woody plant species adapted to the open savanna environment. Moreover, the dependence of carbon‐diversity trade‐offs on the amount of savanna area remaining requires land managers to carefully consider local conditions. Widespread woody encroachment in both Australian and African savannas and grasslands may present similar threats to biodiversity.

Genetic Analysis of the Indri Reveals No Evidence of Distinct Subspecies - Rick A. Brenneman; Adam T. McLain; Justin M. Taylor; John R. Zaonarivelo; Runhua Lei; Susie M. McGuire; Rambinintsoa Andriantompohavana; Anthony B. Rylands; Edward E. Louis (International Journal of Primatology, 2016)

Nonnative plant shifts functional groups of arthropods following drought - Adam B. Mitchell; Andrea R. Litt (Biological Invasions, 2016)

The novel ketamine analog methoxetamine produces dissociative-like behavioral effects in rodents - Adam L. Halberstadt; Natalia Slepak; James Hyun; Mahalah R. Buell; Susan B. Powell (Psychopharmacology, 2016)

Altitudinal shifts of the native and introduced flora of C alifornia in the context of 20th‐century warming - Adam Wolf; Naupaka B. Zimmerman; William R. L. Anderegg; Posy E. Busby; Jon Christensen (Global Ecology and Biogeography, 2016)
Aim The differential responses of plant species to climate change are of great interest and grave concern for scientists and conservationists. One underexploited resource for better understanding these changes are the records held by herbaria. Using these records to assess the responses of different groups of species across the entire flora of California, we sought to quantify the magnitude of species elevational shifts, to measure differences in shifts among functional groups and between native and introduced species, and to evaluate whether these shifts were related to the conservation of thermal niches. Location C alifornia. Methods To characterize these shifts in C alifornia, we used 681,609 georeferenced herbarium records to estimate mean shifts in elevational and climatic space of 4426 plant taxa. We developed and employed a statistical method to robustly analyse the data represented in these records. Results We found that 15% of all taxa in C alifornia have ranges that have shifted upward over the past century. There are significant differences between range shifts of taxa with different naturalization statuses: 12% of endemic taxa show significant upward range shifts, while a greater proportion (27%) of introduced taxa have shifted upward. We found significant differences between the proportion of significant range shifts across taxa with different seed sizes, but did not find evidence for differences in shift based on life‐form (annual versus perennial, herbaceous versus woody). Main conclusions Our analyses suggest that introduced species have disproportionately expanded their ranges upward in elevation over the past century when compared with native species. While these shifts in introduced species may not be exclusively driven by climate, they highlight the importance of considering the interacting factors of climate‐driven range shifts and invasion to understand how floras are responding in the face of anthropogenic change.

Reorganization and expansion of the nidoviral family Arteriviridae - Jens H. Kuhn; Michael Lauck; Adam L. Bailey; Alexey M. Shchetinin; Tatyana V. Vishnevskaya; Yīmíng Bào; Terry Fei Fan Ng; Matthew LeBreton; Bradley S. Schneider; Amethyst Gillis; Ubald Tamoufe; Joseph Le Doux Diffo; et al. (Archives of Virology, 2016)

Pharmacokinetics of Morphine and Its Metabolites in Infants and Young Children After Congenital Heart Surgery - Mohammed H. Elkomy; David R. Drover; Kristi L. Glotzbach; Jeffery L. Galinkin; Adam Frymoyer; Felice Su; Gregory B. Hammer (The AAPS Journal, 2016)

Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2015) - M. J. Adams; E. J. Lefkowitz; A. M. Q. King; D. H. Bamford; M. Breitbart; A. J. Davison; S. A. Ghabrial; A. E. Gorbalenya; N. J. Knowles; P. Krell; R. Lavigne; D. Prangishvili; et al. (Archives of Virology, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Development and characterization of microsatellite loci for Rhinella marina (Amphibia, Bufonidae) and their transferability to two closely related species - Adam R. Bessa-Silva; Divino B. da Cunha; Davidson Sodré; Tom J. O. da Rocha; Horacio Schneider; Iracilda Sampaio; Fernando Sequeira; Marcelo Vallinoto (Conservation Genetics Resources, 2015)

Genetic Data Sharing and Privacy - Marco D. Sorani; John K. Yue; Sourabh Sharma; Geoffrey T. Manley; Adam R. Ferguson; Shelly R. Cooper; Kristen Dams-O’Connor; Wayne A. Gordon; Hester F. Lingsma; Andrew I. R. Maas; David K. Menon; Diane J. Morabito; et al. (Neuroinformatics, 2015)

Serotonin Syndrome Associated with Metaxalone Overdose - Adam R. Bosak; Aaron B. Skolnik (Journal of Medical Toxicology, 2014)

Primary alveolar macrophages exposed to diesel particulate matter increase RAGE expression and activate RAGE signaling - David B. Barton; Bryce C. Betteridge; Tyler D. Earley; Cameron S. Curtis; Adam B. Robinson; Paul R. Reynolds (Cell and Tissue Research, 2014)

Investigation of insecticide leaching from potted nursery stock and aquatic health benefits of bioretention cells receiving nursery runoff - Grant M. Graves; Jason R. Vogel; Jason B. Belden; Eric J. Rebek; Adam M. Simpson (Environmental Science and Pollution Research, 2014)

Spatial and Temporal Assessment of Cumulative Disturbance Impacts Due to Military Training, Burning, Haying, and Their Interactions on Land Condition of Fort Riley - Guangxing Wang; Dana Murphy; Adam Oller; Heidi R. Howard; Alan B. Anderson; Santosh Rijal; Natalie R. Myers; Philip Woodford (Environmental Management, 2014)

Glucagon-like peptide 1 and peptide YY are in separate storage organelles in enteroendocrine cells - Hyun-Jung Cho; Eliza S. Robinson; Leni R. Rivera; Paul J. McMillan; Adam Testro; Mehrdad Nikfarjam; David M. Bravo; John B. Furness (Cell and Tissue Research, 2014)

Electrical and Neurotrophin Enhancement of Neurite Outgrowth Within a 3D Collagen Scaffold - Robert D. Adams; Sara R. Rendell; Lauren R. Counts; Jason B. Papke; Rebecca K. Willits; Amy B. Harkins (Annals of Biomedical Engineering, 2014)

Exploring the spatio-temporal relationship between two key aeroallergens and meteorological variables in the United Kingdom - Nabaz Khwarahm; Jadunandan Dash; Peter M. Atkinson; R. M. Newnham; C. A. Skjøth; B. Adams-Groom; Eric Caulton; K. Head (International Journal of Biometeorology, 2014)

Understanding home range behaviour and resource selection of invasive common brushtail possums (Trichosurus vulpecula) in urban environments - A. L. Adams; M. R. Recio; B. C. Robertson; K. J. M. Dickinson; Y. van Heezik (Biological Invasions, 2013)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Human-mediated drivers of change — impacts on coastal ecosystems and marine biota of South Africa - A Mead; C L Griffiths; G M Branch; C D McQuaid; L K Blamey; J J Bolton; R J Anderson; F Dufois; M Rouault; P W Froneman; A K Whitfield; L R Harris; et al. (African Journal of Marine Science, 2013)

Findings from the Community Health Intervention Program in South Carolina: Implications for Reducing Cancer-Related Health Disparities - James Lyndon McCracken; Daniela B. Friedman; Heather M. Brandt; Swann Arp Adams; Sudha Xirasagar; John R. Ureda; Rachel M. Mayo; Kimberly Comer; Miriam Evans; Delores Fedrick; Jacqueline Talley; Madeline Broderick; et al. (Journal of Cancer Education, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Pollen season and climate: Is the timing of birch pollen release in the UK approaching its limit? - R. M. Newnham; T. H. Sparks; C. A. Skjøth; K. Head; B. Adams-Groom; M. Smith (International Journal of Biometeorology, 2013)

Viral infection of Phaeocystis globosa impedes release of chitinous star‐like structures: quantification using single cell approaches - A. R. Sheik; C. P. D. Brussaard; G. Lavik; R. A. Foster; N. Musat; B. Adam; M. M. M. Kuypers (Environmental Microbiology, 2013)
Summary Phaeocystis globosa is an ecologically important bloom‐forming phytoplankton, which sequesters substantial amounts of inorganic carbon and can form carbon‐enriched chitinous star‐like structures. Viruses infecting P. globosa (PgVs) play a significant regulatory role in population dynamics of the host species. However, the extent to which viruses alter host physiology and its carbon assimilation on single cell level is still largely unknown. This study demonstrates for the first time the impact of viral infection on carbon assimilation and cell morphology of individual axenic P. globosa cells using two single cell techniques: high resolution nanometre‐scale Secondary‐Ion Mass Spectrometry (nanoSIMS) approach and atomic force microscopy (AFM). Up until viral lysis (19 h post infection), the bulk carbon assimilation by infected P. globosa cultures was identical to the assimilation by the non‐infected cultures (33 µmol C l −1 ). However, single cell analysis showed that viral infection of P. globosa impedes the release of star‐like structures. Non‐infected cells transfer up to 44.5 µmol C l −1 (36%) of cellular biomass in the form of star‐like structures, suggesting a vital role in the survival of P. globosa cells. We hypothesize that impediment of star‐like structures in infected P. globosa cells may inactivate viral infectivity by forming flocculants after cell lysis. Moreover, we show that substantial amounts of newly produced viruses (∼ 68%) were attached to P. globosa cells prior to cell lysis. Further, we speculate that infected cells become more susceptible for grazing which provides potential reasons for the sudden disappearance of PgVs in the environment. The scenarios of enhanced grazing is at odds to the current perspective that viral infections facilitates microbial mediated processes by diverting host material away from the higher trophic levels.

Pharmacokinetics and Metabolism of 2-Aminothiazoles with Antiprion Activity in Mice - B. Michael Silber; Satish Rao; Kimberly L. Fife; Alejandra Gallardo-Godoy; Adam R. Renslo; Deepak K. Dalvie; Kurt Giles; Yevgeniy Freyman; Manuel Elepano; Joel R. Gever; Zhe Li; Matthew P. Jacobson; et al. (Pharmaceutical Research, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

High Content Evaluation of Shear Dependent Platelet Function in a Microfluidic Flow Assay - Ryan R. Hansen; Adam R. Wufsus; Steven T. Barton; Abimbola A. Onasoga; Rebecca M. Johnson-Paben; Keith B. Neeves (Annals of Biomedical Engineering, 2013)

Clinical characteristics of children with lower respiratory tract infections are dependent on the carriage of specific pathogens in the nasopharynx - T. Tenenbaum; A. Franz; N. Neuhausen; R. Willems; J. Brade; S. Schweitzer-Krantz; O. Adams; H. Schroten; B. Henrich (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Anaerobic methane oxidation in metalliferous hydrothermal sediments: influence on carbon flux and decoupling from sulfate reduction - Scott D. Wankel; Melissa M. Adams; David T. Johnston; Colleen M. Hansel; Samantha B. Joye; Peter R. Girguis (Environmental Microbiology, 2012)
Summary The anaerobic oxidation of methane (AOM) is a globally significant sink that regulates methane flux from sediments into the oceans and atmosphere. Here we examine mesophilic to thermophilic AOM in hydrothermal sediments recovered from the Middle Valley vent field, on the Juan de Fuca Ridge. Using continuous‐flow sediment bioreactors and batch incubations, we characterized (i) the degree to which AOM contributes to net dissolved inorganic carbon flux, (ii) AOM and sulfate reduction (SR) rates as a function of temperature and (iii) the distribution and density of known anaerobic methanotrophs (ANMEs). In sediment bioreactors, inorganic carbon stable isotope mass balances results indicated that AOM accounted for between 16% and 86% of the inorganic carbon produced, underscoring the role of AOM in governing inorganic carbon flux from these sediments. At 90°C, AOM occurred in the absence of SR, demonstrating a striking decoupling of AOM from SR. An abundance of Fe(III)‐bearing minerals resembling mixed valent Fe oxides, such as green rust, suggests the potential for a coupling of AOM to Fe(III) reduction in these metalliferous sediments. While SR bacteria were only observed in cooler temperature sediments, ANMEs allied to ANME‐1 ribotypes, including a putative ANME‐1c group, were found across all temperature regimes and represented a substantial proportion of the archaeal community. In concert, these results extend and reshape our understanding of the nature of high temperature methane biogeochemistry, providing insight into the physiology and ecology of thermophilic anaerobic methanotrophy and suggesting that AOM may play a central role in regulating biological dissolved inorganic carbon fluxes to the deep ocean from the organic‐poor, metalliferous sediments of the global mid‐ocean ridge hydrothermal vent system.

Ultra-structural identification of interstitial cells of Cajal in the zebrafish Danio rerio - Evan R. Ball; Miho M. Matsuda; Louis Dye; Victoria Hoffmann; Patricia M. Zerfas; Eva Szarek; Adam Rich; Ajay B. Chitnis; Constantine A. Stratakis (Cell and Tissue Research, 2012)

Creating a Cadre of Junior Investigators to Address the Challenges of Cancer-Related Health Disparities: Lessons Learned from the Community Networks Program - Tisha M. Felder; Heather M. Brandt; Cheryl A. Armstead; Philip P. Cavicchia; Kathryn L. Braun; Swann A. Adams; Daniela B. Friedman; Sora Tanjasiri; Susan E. Steck; Emily R. Smith; Virginie G. Daguisé; James R. Hébert (Journal of Cancer Education, 2012)

Examining the effects of former cannabis use on cerebellum-dependent eyeblink conditioning in humans - Adam B. Steinmetz; Chad R. Edwards; Jennifer M. Vollmer; Molly A. Erickson; Brian F. O’Donnell; William P. Hetrick; Patrick D. Skosnik (Psychopharmacology, 2012)

A 7 Tesla fMRI Study of Amygdala Responses to Fearful Faces - Wietske van der Zwaag; Sandra E. Da Costa; Nicole R. Zürcher; Reginald B. Adams; Nouchine Hadjikhani (Brain Topography, 2012)

Reducing Cancer Disparities Through Innovative Partnerships: A Collaboration of the South Carolina Cancer Prevention and Control Research Network and Federally Qualified Health Centers - Daniela B. Friedman; Vicki M. Young; Darcy A. Freedman; Swann Arp Adams; Heather M. Brandt; Sudha Xirasagar; Tisha M. Felder; John R. Ureda; Thomas Hurley; Leepao Khang; Dayna Campbell; James R. Hébert (Journal of Cancer Education, 2012)

Changes in the fish community of Loch Leven: untangling anthropogenic pressures - I. J. Winfield; C. E. Adams; J. D. Armstrong; R. Gardiner; A. Kirika; J. Montgomery; B. M. Spears; D. C. Stewart; J. E. Thorpe; W. Wilson (Hydrobiologia, 2012)

High-Resolution Fibre-Optic Temperature Sensing: A New Tool to Study the Two-Dimensional Structure of Atmospheric Surface-Layer Flow - Christoph K. Thomas; Adam M. Kennedy; John S. Selker; Ayla Moretti; Martin H. Schroth; Alexander R. Smoot; Nicholas B. Tufillaro; Matthias J. Zeeman (Boundary-Layer Meteorology, 2012)

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

Comparison of the Effects of Antimicrobial Agents from Three Different Classes on Metabolism of Isoflavonoids by Colonic Microflora Using Etest Strips - John B. Sutherland; Brad M. Bridges; Thomas M. Heinze; Michael R. Adams; Patrick J. Delio; Charlotte Hotchkiss; Fatemeh Rafii (Current Microbiology, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Intra-seasonal variation in foraging behavior among Adélie penguins (Pygocelis adeliae) breeding at Cape Hallett, Ross Sea, Antarctica - P. O’B. Lyver; C. J. MacLeod; G. Ballard; B. J. Karl; K. J. Barton; J. Adams; D. G. Ainley; P. R. Wilson (Polar Biology, 2011)

A biomarker of mercury body-burden correlated with diagnostic domain specific clinical symptoms of autism spectrum disorder - Janet K. Kern; David A. Geier; James B. Adams; Mark R. Geier (BioMetals, 2010)

Ecosystem Carbon Storage Across the Grassland–Forest Transition in the High Andes of Manu National Park, Peru - Adam Gibbon; Miles R. Silman; Yadvinder Malhi; Joshua B. Fisher; Patrick Meir; Michael Zimmermann; Greta C. Dargie; William R. Farfan; Karina C. Garcia (Ecosystems, 2010)

The complete genome sequence of Canna yellow streak virus - W. A. Monger; I. P. Adams; R. H. Glover; B. Barrett (Archives of Virology, 2010)

An evaluation of the usefulness of Staphylococcus aureus serodiagnosis in clinical practice - J. Elston; M. Ling; B. Jeffs; K. Adams; H. Thaker; P. Moss; R. Meigh; G. Barlow (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

The distribution and host range of the pandemic disease chytridiomycosis in Australia, spanning surveys from 1956–2007 - Kris Murray; Richard Retallick; Keith R. McDonald; Diana Mendez; Ken Aplin; Peter Kirkpatrick; Lee Berger; David Hunter; Harry B. Hines; R. Campbell; Matthew Pauza; Michael Driessen; et al. (Ecology, 2010)
Chytridiomycosis is the worst disease to affect vertebrate biodiversity on record. In Australia, it is thought to have caused the extinction of four frog species, and it threatens the survival of at least 10 more. We report the current distribution and host range of this invasive disease in Australia, which is essential knowledge for conservation management. We envisage that the data be used in a global and national context for predictive modeling, meta‐analyses, and risk assessment. Our continent‐wide data set comprises 821 sites in Australia and includes 10 183 records from >80 contributors spanning collection dates from 1956 to 2007. Sick and dead frogs from the field and apparently healthy frogs from museum collections were tested opportunistically for the presence of Batrachochytrium dendrobatidis , the fungal pathogen causing chytridiomycosis, and apparently healthy frogs and tadpoles found during surveys were tested purposively. The diagnostic tests used were histology of skin samples and quantitative PCR of skin swabs. Chytridiomycosis was found in all Australian states and the Australian Capital Territory, but not in the Northern Territory. Currently it appears to be confined to the relatively cool and wet areas of Australia, such as along the Great Dividing Range and adjacent coastal areas in the eastern mainland states of Queensland, New South Wales, and Victoria, eastern and central Tasmania, southern South Australia, and southwestern Western Australia. Batrachochytrium dendrobatidis may have been introduced into Australia via the port of Brisbane around 1978 and spread northward and southward. It did not appear to arrive in Western Australia until 1985. The earliest records from South Australia and Tasmania are from 1995 and 2004, respectively, although archival studies from these states are lacking. We also report negative findings showing that the disease does not currently occur in some areas that appear to be environmentally suitable, including Cape York Peninsula in Queensland and most of the World Heritage Area in western Tasmania. Infection with B. dendrobatidis has been recorded from 63 frog species in Australia to date, all belonging to the Hylidae, Limnodynastidae, and Myobatrachidae, with the exception of one individual of a species from the Microhylidae and the introduced cane toad of the family Bufonidae. The complete data sets corresponding to abstracts published in the Data Papers section of the journal are published electronically in Ecological Archives at 〈 http://esapubs.org/archive 〉. (The accession number for each Data Paper is given directly beneath the title.)

No Differences in Soil Carbon Stocks Across the Tree Line in the Peruvian Andes - Michael Zimmermann; Patrick Meir; Miles R. Silman; Anna Fedders; Adam Gibbon; Yadvinder Malhi; Dunia H. Urrego; Mark B. Bush; Kenneth J. Feeley; Karina C. Garcia; Greta C. Dargie; Wiliam R. Farfan; et al. (Ecosystems, 2010)

Nutritional Ecology of Ateles chamek in lowland Bolivia: How Macronutrient Balancing Influences Food Choices - Annika M. Felton; Adam Felton; Jeff T. Wood; William J. Foley; David Raubenheimer; Ian R. Wallis; David B. Lindenmayer (International Journal of Primatology, 2009)

Climate change, conservation and management: an assessment of the peer-reviewed scientific journal literature - Adam Felton; Joern Fischer; David B. Lindenmayer; Rebecca Montague-Drake; Arianne R. Lowe; Debbie Saunders; Annika M. Felton; Will Steffen; Nicola T. Munro; Kara Youngentob; Jake Gillen; Phil Gibbons; et al. (Biodiversity and Conservation, 2009)

Premature Decline of Eucalyptus and Altered Ecosystem Processes in the Absence of Fire in Some Australian Forests - D. C. Close; N. J. Davidson; D. W. Johnson; M. D. Abrams; S. C. Hart; I. D. Lunt; R. D. Archibald; B. Horton; M. A. Adams (The Botanical Review, 2009)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

A case–control study of childhood brain tumors and fathers’ hobbies: a Children’s Oncology Group study - Andrea L. Rosso; Mary E. Hovinga; Lucy B. Rorke-Adams; Logan G. Spector; Greta R. Bunin (Cancer Causes & Control, 2008)

Evaluation of the INNO‐LiPA mycobacteria v2 assay for identification of aquatic mycobacteria - F Pourahmad; K D Thompson; J B Taggart; A Adams; R H Richards (Journal of Fish Diseases, 2008)
Fifty‐seven isolates of mycobacteria comprising 10 reference strains, 47 field isolates and one non‐ Mycobacterium isolate were screened using commercial INNO‐LiPA v2 assay kits. All mycobacteria isolates tested hybridized with the Mycobacterium genus probe on the LiPA strip. All M. marinum , M. fortuitum and M. chelonae reference and field strains and three out of the four M. gordonae isolates hybridized to their corresponding species‐ or complex‐specific probes. Two cultures (a type strain and a field isolate) yielded mixed growth of two mycobacterial species, i.e. M. chelonae and M. fortuitum. A Mycobacterium isolate from one of these cultures was subsequently purified and correctly identified with the kit. However, sequence analysis of the 16S–23S rRNA internal transcribed spacer (ITS) region of various mycobacteria isolates revealed a misidentification of M. shottsii and M. pseudoshottsii with the kit because these isolates reacted with the M. marinum / M. ulcerans probe. Moreover, nine of the 13 field isolates presumed to be M. fortuitum from the results of the kit had closer ITS sequence homology with M. conceptionense , a species which, to our knowledge, has never been reported in fish. These findings highlight the need to redesign the M. fortuitum – M. peregrinum probe included in the INNO‐LiPA assay and to introduce additional complex‐specific probes into the kit. Nevertheless, the kit proved to be a rapid and reliable method for identifying mycobacteria in the aquatic environment and would be particularly useful in laboratories without sequencing facilities.

Modification of the effects of 5-methoxy-N,N-dimethyltryptamine on exploratory behavior in rats by monoamine oxidase inhibitors - Adam L. Halberstadt; Mahalah R. Buell; Virginia L. Masten; Victoria B. Risbrough; Mark A. Geyer (Psychopharmacology, 2008)

Biological Responses to Contrasting Hydrology in Backwaters of Upper Mississippi River Navigation Pool 25 - Michael B. Flinn; S. Reid Adams; Matt R. Whiles; James E. Garvey (Environmental Management, 2008)

Phylogenetic relationships among North American Alosa species (Clupeidae) - B. R. Bowen; B. R. Kreiser; P. F. Mickle; J. F. Schaefer; S. B. Adams (Journal of Fish Biology, 2008)
A phylogeny of the six North American species in the genus Alosa , with representatives of three Eurasian species, was generated using mtDNA sequences. This was accomplished by obtaining sequences for three North American species and additional geographical sampling of the other three species. The subgenus Alosa , including the formerly recognized subgenus Caspialosa , formed a strongly supported monophyletic group. Alosa alabamae was part of a polytomy with Alosa sapidissima , which was interpreted to support the recognition of A. alabamae as an incipient, yet distinct, species. The subgenus Pomolobus was not recovered as a monophyletic group. Alosa chrysochloris was basal to all other Alosa , although this position was only weakly supported. Previous work had indicated that Alosa pseudoharengus and Alosa aestivalis are not reciprocally monophyletic, but additional sampling in this study did not detect any further cases of shared haplotypes between the two species. The phylogeny supports previous hypotheses that the evolution of North American Alosa species in the Gulf of Mexico ( A. chrysochloris and A. alabamae ) was the result of two independent events. First, the ancestor of A. chrysochloris was isolated in the Gulf of Mexico, likely by the close of the Suwannee Straits, and this was followed later by dispersal of the ancestor of A. alabamae around the Florida peninsula into the Gulf of Mexico sometime during or after the Pleistocene.

Over-expression of a gibberellin 2-oxidase gene from Phaseolus coccineus L. enhances gibberellin inactivation and induces dwarfism in Solanum species - C. Dijkstra; E. Adams; A. Bhattacharya; A. F. Page; P. Anthony; S. Kourmpetli; J. B. Power; K. C. Lowe; S. G. Thomas; P. Hedden; A. L. Phillips; M. R. Davey (Plant Cell Reports, 2008)

Renal myxozoanosis in weedy sea dragons, Phyllopteryx taeniolatus (Lacepède), caused by Sinuolinea phyllopteryxa n. sp. - M M Garner; S D Atkinson; S L Hallett; J L Bartholomew; R W Nordhausen; H Reed; L Adams; B Whitaker (Journal of Fish Diseases, 2008)
Renal myxozoanosis was diagnosed histologically in 11 captive, wild caught, adult weedy (common) sea dragons, Phyllopteryx taeniolatus , from three separate public aquaria in the United States. Myxozoan spores were visible in wet mounts of kidney tissue and were associated with renal tubular dilatation and tubular epithelial cell hypertrophy. Light and electron microscopy revealed spore morphology consistent with the genus Sinuolinea . Spores were spheroidal, slightly dorso‐ventrally compressed, length ( L ) 17.1 × width ( W ) 16.4 × thickness ( T ) 15.6 μm, with two shell valves joined at a distinct, sinuous sutural ridge, and had two nearly spherical polar capsules, L 5.5 × W 5.0 μm, with five to seven turns of the polar filament. There were no extra‐valvular ridges or protrusions. DNA sequencing required the design of three new primers that yielded 1740 bp of 18S ribosomal DNA sequence. The parasite was determined to be novel based on morphological and molecular data, and was given the name Sinuolinea phyllopteryxa after its vertebrate host.

Differential gene flow of mitochondrial and nuclear DNA markers among chromosomal races of Australian morabine grasshoppers ( Vandiemenella, viatica species group) - T. KAWAKAMI; R. K. BUTLIN; M. ADAMS; K. M. SAINT; D. J. PAULL; S. J. B. COOPER (Molecular Ecology, 2007)
Recent theoretical developments have led to a renewed interest in the potential role of chromosomal rearrangements in speciation. Australian morabine grasshoppers (genus Vandiemenella , viatica species group) provide an excellent study system to test this potential role of chromosomal rearrangements because they show extensive chromosomal variation and formed the basis of a classic chromosomal speciation model. There are three chromosomal races, viatica 19, viatica 17, and P24(XY), on Kangaroo Island, South Australia, forming five parapatric populations with four putative contact zones among them. We investigate the extent to which chromosomal variation among these populations may be associated with barriers to gene flow. Population genetic and phylogeographical analyses using 15 variable allozyme loci and the elongation factor‐1α ( EF‐1 α) gene indicate that the three races represent genetically distinct taxa. In contrast, analyses of the mitochondrial cytochrome c oxidase subunit I ( COI ) gene show the presence of three distinctive and geographically localized groups that do not correspond with the distribution of the chromosomal races. These discordant population genetic patterns are likely to result from introgressive hybridization between the chromosomal races and range expansions/contractions. Overall, these results suggest that reduction of nuclear gene flow may be associated with chromosomal variation, or underlying genetic variation linked with chromosomal variation, whereas mitochondrial gene flow appears to be independent of this variation in these morabine grasshoppers. The identification of an intact contact zone between P24(XY) and viatica 17 offers considerable potential for further investigation of molecular mechanisms that maintain distinct nuclear genomes among the chromosomal races.

Stress does not inhibit induced vitellogenesis in juvenile rainbow trout - Adam R. Schwindt; Grant W. Feist; Carl B. Schreck (Environmental Biology of Fishes, 2007)

Determination of Iodine in Low Mass Human Hair Samples by Inductively Coupled Plasma Mass Spectrometry - K. E. Levine; A. S. Essader; F. X. Weber; J. M. Perlmutter; L. S. Milstein; R. A. Fernando; M. A. Levine; B. J. Collins; J. B. Adams; P. M. Grohse (Bulletin of Environmental Contamination and Toxicology, 2007)

Paleolimnological assessment of human impacts on an urban South African lake - F. García-Rodríguez; C. R. Anderson; J. B. Adams (Journal of Paleolimnology, 2007)

The southernmost worm, Scottnema lindsayae (Nematoda): diversity, dispersal and ecological stability - B. J. Adams; D. H. Wall; U. Gozel; A. R. Dillman; J. M. Chaston; I. D. Hogg (Polar Biology, 2007)

Feeding Selectivity by Mantled Howler Monkeys (Alouatta palliata) in Relation to Leaf Secondary Chemistry in Hymenaea courbaril - B. J. Welker; W. König; M. Pietsch; R. P. Adams (Journal of Chemical Ecology, 2007)

Paleolimnological evidence of Holocene climatic changes in Lake Blanca, southern Uruguay - L. del Puerto; F. García-Rodríguez; H. Inda; R. Bracco; C. Castiñeira; J. B. Adams (Journal of Paleolimnology, 2006)

Relationships between Trophic State, Paleosalinity and Climatic Changes during the First Holocene Marine Transgression in Rocha Lagoon, Southern Uruguay - H. Inda; F. García-Rodríguez; L. del Puerto; V. Acevedo; D. Metzeltin; C. Castiñeira; R. Bracco; J. B. Adams (Journal of Paleolimnology, 2006)

Maternal Diet During Pregnancy and its Association with Medulloblastoma in Children: A Children’s Oncology Group Study (United States) - Greta R. Bunin; Lawrence H. Kushi; Paul R. Gallagher; Lucy B. Rorke-Adams; Mary L. McBride; Avital Cnaan (Cancer Causes & Control, 2005)

Distribution Patterns of Lentic-Breeding Amphibians in Relation to Ultraviolet Radiation Exposure in Western North America - Michael J. Adams; Blake R. Hossack; Roland A. Knapp; Paul Stephen Corn; Stephen A. Diamond; Peter C. Trenham; Dan B. Fagre (Ecosystems, 2005)

Genetic and physical mapping of the grapevine powdery mildew resistance gene, Run1, using a bacterial artificial chromosome library - C. L. Barker; T. Donald; J. Pauquet; M. B. Ratnaparkhe; A. Bouquet; A.-F. Adam-Blondon; M. R. Thomas; I. Dry (Theoretical and Applied Genetics, 2005)

Construction and characterization of BAC libraries from major grapevine cultivars - A-F Adam-Blondon; A. Bernole; G. Faes; D. Lamoureux; S. Pateyron; M. S. Grando; M. Caboche; R. Velasco; B. Chalhoub (Theoretical and Applied Genetics, 2005)

Transcriptional program of bone morphogenetic protein-2-induced epithelial and smooth muscle differentiation of pluripotent human embryonal carcinoma cells - Rajendrakumar S. V. Chadalavada; Jane Houldsworth; Adam B. Olshen; George J. Bosl; Lorenz Studer; R. S. K. Chaganti (Functional & Integrative Genomics, 2005)

Mitochondrial DNA and RAPD polymorphisms in the haploid mite Brevipalpus phoenicis (Acari: Tenuipalpidae) - J. C. V. Rodrigues; M. Gallo-meagher; R. Ochoa; C. C. Childers; B. J. Adams (Experimental and Applied Acarology, 2004)

Airborne Pollen and Fungal Spores in Florist Shops in Worcester and in Bristol, UK: A Potential Problem for Occupational Health - J Emberlin; B Adams-Groom; R Treu; F Carswell (Aerobiologia, 2004)

Using faecal DNA sampling and GIS to monitor hybridization between red wolves ( Canis rufus ) and coyotes ( Canis latrans ) - J. R. Adams; B. T. Kelly; L. P. Waits (Molecular Ecology, 2003)
The US Fish and Wildlife Service's (USFWS) Red Wolf Recovery Program recognizes hybridization with coyotes as the primary threat to red wolf recovery. Efforts to curb or stop hybridization are hampered in two ways. First, hybrid individuals are difficult to identify based solely on morphology. Second, managers need to effectively search 6000 km 2 for the presence of coyotes and hybrids. We develop a noninvasive method to screen large geographical areas for coyotes and hybrids with maternal coyote ancestry by combining mitochondrial DNA sequence analysis of faeces (scat) and geographic information system (GIS) technology. This method was implemented on the Alligator River National Wildlife Refuge (1000 km 2 ) in northeastern North Carolina. A total of 956 scats were collected in the spring of 2000 and 2001 and global positioning system (GPS) coordinates were recorded. Seventy‐five percent of the scats were assigned to species and five coyote/hybrid scats were detected. Placement of scat location coordinates on a map of the experimental population area revealed that four of the coyote/hybrid scats were detected within the home ranges of sterilized hybrids. The other coyote/hybrid scat indicated the presence of a previously unknown individual. We suggest this method be expanded to include more of the experimental population area and be optimized for use with nuclear markers to improve detection of hybrid and back‐crossed individuals.

Diadema antillarum 17 years after mass mortality: is recovery beginning on St. Croix? - R. J. Miller; A. J. Adams; N. B. Ogden; J. C. Ogden; J. P. Ebersole (Coral Reefs, 2003)

Above‐ and below‐ground responses of C 3 –C 4 species mixtures to elevated CO 2 and soil water availability - JUSTIN D. DERNER; HYRUM B. JOHNSON; BRUCE A. KIMBALL; PAUL J. PINTER; H. Wayne POLLEY; CHARLES R. TISCHLER; THOMAS W. BOUTTON; ROBERT L. LAMORTE; GERALD W. WALL; NEIL R. ADAM; STEVEN W. LEAVITT; MICHAEL J. OTTMAN; et al. (Global Change Biology, 2003)
We evaluated the influences of CO 2 [Control, ∼ 370 µ mol mol − 1 ; 200 µ mol mol − 1 above ambient applied by free‐air CO 2 enrichment (FACE)] and soil water (Wet, Dry) on above‐ and below‐ground responses of C 3 (cotton, G ossypium hirsutum ) and C 4 (sorghum, Sorghum bicolor ) plants in monocultures and two density mixtures. In monocultures, CO 2 enrichment increased height, leaf area, above‐ground biomass and reproductive output of cotton, but not sorghum, and was independent of soil water treatment. In mixtures, cotton, but not sorghum, above‐ground biomass and height were generally reduced compared to monocultures, across both CO 2 and soil water treatments. Density did not affect individual plant responses of either cotton or sorghum across the other treatments. Total (cotton + sorghum) leaf area and above‐ground biomass in low‐density mixtures were similar between CO 2 treatments, but increased by 17–21% with FACE in high‐density mixtures, due to a 121% enhancement of cotton leaf area and a 276% increase in biomass under the FACE treatment. Total root biomass in the upper 1.2 m of the soil was not influenced by CO 2 or by soil water in monoculture or mixtures; however, under dry conditions we observed significantly more roots at lower soil depths ( > 45 cm). Sorghum roots comprised 81–85% of the total roots in the low‐density mixture and 58–73% in the high‐density mixture. CO 2 ‐enrichment partly offset negative effects of interspecific competition on cotton in both low‐ and high‐density mixtures by increasing above‐ground biomass, with a greater relative increase in the high‐density mixture. As a consequence, CO 2 ‐enrichment increased total above‐ground yield of the mixture at high density. Individual plant responses to CO 2 enrichment in global change models that evaluate mixed plant communities should be adjusted to incorporate feedbacks for interspecific competition. Future field studies in natural ecosystems should address the role that a CO 2 ‐mediated increase in C 3 growth may have on subsequent vegetation change.

Control of hyperhydricity in Eucalyptus axillary shoot cultures grown in liquid medium - Adam B. Whitehouse; Timothy R. Marks; Glyn A. Edwards (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Identification of resistance gene analogs linked to a powdery mildew resistance locus in grapevine - T. M. Donald; F. Pellerone; A.-F. Adam-Blondon; A. Bouquet; M. R. Thomas; I. B. Dry (Theoretical and Applied Genetics, 2002)

Molecular mechanisms of deoxynivalenol resistance in the yeastSaccharomyces cerevisiae - G Adam; R Mitterbauer; A Raditschnig; B Poppenberger; T Karl; S Goritschnig; H Weindorfer; J Glössl (Mycotoxin Research, 2001)

Chronic rejection: The result of uncontrolled remodelling of graft tissue by recipient mesenchymal cells? Data from two rodent models and the effects of immunosupressive therapies - T. R. Brazelton; B. Adams; R. Shorthouse; R. E. Morris (Inflammation Research, 1999)

Alcohol dehydrogenase 3 genotype modification of the associationof alcohol consumption with breast cancer risk - Jo L. Freudenheim; Christine B. Ambrosone; Kirsten B. Moysich; John E. Vena; Saxon Graham; James R. Marshall; Paola Muti; Rosemary Laughlin; Takuma Nemoto; Lea C. Harty; G. Adam Crits; Arthur W.K. Chan; et al. (Cancer Causes & Control, 1999)

Quantitative Determination of Gap Junctional Permeability in the Lens Cortex - R. Eckert; B. Adams; J. Kistler; P. Donaldson (The Journal of Membrane Biology, 1999)

Effects of reforestation methods on genetic diversity of lodgepole pine: an assessment using microsatellite and randomly amplified polymorphic DNA markers - B. R. Thomas; S. E. Macdonald; M. Hicks; D. L. Adams; R. B. Hodgetts (Theoretical and Applied Genetics, 1999)

Short tandem repeat polymorphic markers for the rat genome from marker-selected libraries - Roxanne Y. Walder; Michael R. Garrett; Ann M. McClain; Gretel E. Beck; Theresa M.H. Brennan; Nancy A. Kramer; Adam B. Kanis; Allyn L. Mark; John P. Rapp (Mammalian Genome, 1998)

Trophic polymorphism amongst Arctic charr from Loch Rannoch, Scotland - C. E. Adams; D. Fraser; F. A. Huntingford; R. B. Greer; C. M. Askew; A. F. Walker (Journal of Fish Biology, 1998)
This paper describes the results of a multivariate and univariate morphometric analysis of three groups of Arctic charr Salvelinus alpinus from Loch Rannoch, Perthshire, Scotland, distinguished a priori on the basis of coloration (bright v. cryptic) and site of capture (from two locations 12 km apart). The analysis produced a clear and highly significant distinction, not only between brightly and cryptically coloured charr, but also between the two cryptically coloured groups, one of which was more robust in terms of several size‐independent head measurements. Stomach analysis showed that the brightly coloured charr fed entirely on zooplankton, the less robust, cryptically coloured fish, fed on benthic macroinvertebrates, whereas a significant proportion of the diet of the more robust cryptically‐coloured form consisted of other fish. Differences in length at age also distinguished the three forms, with the robust, piscivorous charr, which live longer and potentially reach a larger final size, attaining smaller sizes at a given age. These data clearly confirm the previous identification of a distinct planktivorous morph of Arctic charr in Loch Rannoch and extend the morph analysis by distinguishing two additional morphs, a benthivorous morph and a piscivorous morph that are morphologically and ecologically distinct. The results are discussed in the context of other systems in which sympatric morphs of Arctic charr have been described.

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Validation of a simple potato growth model in the North Central United States - K. B. Johnson; R. L. Conlon; S. S. Adams; D. C. Nelson; D. I. Rouse; P. S. Teng (American Journal of Potato Research, 1988)

Trace metals in organisms from ocean disposal sites of the middle eastern United States - R. A. Greig; D. R. Wenzloff; A. Adams; B. Nelson; C. Shelpuk (Archives of Environmental Contamination and Toxicology, 1977)

Potato foliage development - R. A. Kelley; J. B. Adams; P. H. Baird (American Journal of Potato Research, 1953)

Potato aphid control studies, 1946–1949, at Woodstock, N. B., Canada - J. B. Adams; R. A. Kelley (American Journal of Potato Research, 1950)